Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
shortDOI: 10/f63z7b KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2015.01.001 10/f63z7b 2339240:76EQG2NV 2405685:LM7EYD5E 2405685:WU59KPEH 261495:QBFNURGR
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Piper, Benjamin; Jepkemei, Evelyn; Kwayumba, Dunston; Kibukho, Kennedy (FIRE: Forum for International Research in Education, 2015)
Kenya is investing in information and communication technology (ICT) to improve children's learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students. All three showed significant impacts in English and Kiswahili above the results of the control group. The impacts of the three interventions were not statistically significantly different from each other. Based on the findings, we recommend that Kenyan policy makers embed ICT interventions in a larger instructional reform, using ICT to support particular instructional improvement challenges. We also suggest that policy makers incorporate empirically derived cost-effectiveness analysis into investment decisions, to ensure that ICT provides value for money.
shortDOI: 10/ggjkvv KerkoCite.ItemAlsoKnownAs: 10.18275/fire201502011025 10/ggjkvv 2339240:APPT498R 2339240:D5IHJW9H 2339240:E5GA8GCG 2339240:EK3GAM3J 2339240:G6TBKSGI 2339240:IYCXFMIU 2405685:5IT5XZNT 2405685:DAU3FLGU 2405685:H9RNSJQE 2405685:J45J4EMF 2405685:V6F62IW5 2405685:WVNEPIB3 2405685:Y4AUMNW2 2534378:73A9DFAH 2534378:8Y5PJAGB 2534378:P2EJKSKD
Keywords: African Languages; Control Groups; Cost Effectiveness; ERIC; Current Index to Journals in Education (CIJE); Educational Policy; Educational Practices; Elementary Secondary Education; English (Second Language); Experimental Groups; Foreign Countries; Handheld Devices; Intervention; Kenya; Literacy; Outcomes of Education; Program Effectiveness; Randomized Controlled Trials; Reading Achievement; Student Improvement; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096974; ___working_potential_duplicate; __finaldtb

Inclusive educational practices in Kenya: Evidencing practice of itinerant teachers who work with children with visual impairment in local mainstream schools - Lynch, Paul; McCall, Steve; Douglas, Graeme; McLinden, Mike; Mogesa, Bernard; Mwaura, Martha; Muga, John; Njoroge, Michael (International Journal of Educational Development, 2011)
This article presents a findings from an investigation of the work of 38 specialist itinerant teachers (ITs) supporting the educational inclusion of children with visual impairment in Kenya. The research was designed around a participatory action research framework involving in-country researchers and participants (teachers) working in collaboration with researchers in the United Kingdom. Following an introductory training workshop, participants kept research journals over a 2-month period in which they recorded details of their itinerant duties (including the processes and content of their visits). Findings provide information about local practices of ITs support for children with visual impairment in mainstream schools and raise broader questions about the barriers to learning and development facing children with disabilities in mainstream schools in Kenya and other developing countries.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2010.08.006 2339240:99E5PNBZ 2405685:F3M4BRIW
Keywords: Inclusive education; Itinerant teachers; Kenya; Participatory action research; Visual impairment

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.
shortDOI: 10/gfw2mk KerkoCite.ItemAlsoKnownAs: 10.1080/2331186X.2016.1139439 10/gfw2mk 2405685:K8ZKUDQE

Genetics problem solving in high school testing in Kenya: Effects of metacognitive prompting during testing - Aurah, Catherine M; Cassady, Jerrell Craig; McConnell, Tom John (Electronic Journal for Research in Science and Mathematics Education, 2014)
This study investigated the effectiveness of using metacognitive prompts during testing for improving results in a Genetics Problem Solving Test (GPST). The study, a pre-test post-test, control group quasi-experimental design involving 2x2x2 analysis of covariance (ANCOVA) also investigated the moderating effects of gender and school type. A total of 2,138 high school students purposively selected from seventeen high schools in Western province, Kenya, participated in the study using three validated instruments; Biology Ability Test (BAT), Genetics Problem Solving Test (GPST), and Metacognitive Prompting Questionnaire (MPQ). Findings showed that metacognitive prompting (MP) had a significant effect on students’ genetics problem solving ability, F(1, 2137) = 10.909, p < 0.001. The findings also revealed gender differences, with girls outperforming boys on the genetics problem solving test. Furthermore, a significant interaction between metacognitive prompting and school type showed that students in provincial schools benefited from MPs more than students from district schools. This study established a foundation for instructional methods for biology teachers and recommendations are made for implementing metacognitive prompting in a problem-based learning environment in high schools and science teacher education programs in Kenya.
KerkoCite.ItemAlsoKnownAs: 2339240:G5AWLGH3 2405685:6QCF8TS7
Keywords: ⛔ No DOI found

Improving Literacy Instruction in Kenya Through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial - Jukes, Matthew C. H.; Turner, Elizabeth L.; Dubeck, Margaret M.; Halliday, Katherine E.; Inyega, Hellen N.; Wolf, Sharon; Zuilkowski, Stephanie Simmons; Brooker, Simon J. (Journal of Research on Educational Effectiveness, 2017)
We evaluated a program to improve literacy instruction on the Kenyan coast using training workshops, semiscripted lesson plans, and weekly text-message support for teachers to understand its impact on students’ literacy outcomes and on the classroom practices leading to those outcomes. The evaluation ran from the beginning of Grade 1 to the end of Grade 2 in 51 government primary schools chosen at random, with 50 schools acting as controls. The intervention had an impact on classroom practices with effect sizes from 0.57 to 1.15. There was more instruction with written text and more focus on letters and sounds. There was a positive impact on three of four primary measures of children’s literacy after two years, with effect sizes up to 0.64, and school dropout reduced from 5.3% to 2.1%. This approach to literacy instruction is sustainable, and affordable and a similar approach has subsequently been adopted nationally in Kenya.
shortDOI: 10/gftrwn KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2016.1221487 10/gftrwn 2339240:BHTFCPZY 2339240:NZ4F4CI7 2339240:WQWT3F9T 2405685:8RA9QUBS 2405685:KF3AT824 2405685:L29LKK2H 2405685:NZMWQR53 2405685:ZPZ33ATM 2534378:5AX7B2XZ 2534378:69A797YC 2534378:6YQFC9JR 2534378:DNVP68DF 2534378:JCAY2TT6 2534378:LP5IEPIP 2534378:M4JQTSXE 2534378:NJKCAKUT
Keywords: Africa; Classroom Observation Techniques; Dropout Rate; ERIC; Current Index to Journals in Education (CIJE); Early Childhood Education; Effect Size; Elementary Education; Elementary School Students; Elementary School Teachers; Faculty Development; Foreign Countries; Grade 1; Grade 2; Handheld Devices; Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs; Intelligence Tests; Intervention; Interviews; Kenya; Literacy Education; Maximum Likelihood Statistics; Pretests Posttests; Primary Education; Program Effectiveness; Promising Interventions Are Great; but Are They Enough?; Questionnaires; RCT; Randomized Controlled Trials; Raven Progressive Matrices; Rural Schools; Statistical Analysis; Teacher Improvement; Teaching Methods; Telecommunications; What We Are Learning About Early Education in Sub-Saharan Africa; __:import:01; __:match:final; __:matched; __:study_id:2096051; ___working_potential_duplicate; __finaldtb; early grade reading; literacy instruction

Improving procedural and conceptual mathematics outcomes: evidence from a randomised controlled trial in Kenya - Piper, Benjamin; Ralaingita, Wendi; Akach, Linda; King, Simon (Journal of Development Effectiveness, 2016)
To improve learning outcomes, an intervention in Kenya called the Primary Math and Reading (PRIMR) Initiative provided pupil learning materials, teachers’ guides and modest teacher professional development in mathematics. This paper presents the causal impact of PRIMR’s mathematics intervention on pupil achievement indices for procedural and conceptual numeracy, using a diﬀerences-in-diﬀerences analytic strategy. The mathematics intervention produced modest, statistically signiﬁcant results: generally similar results for males and females, a larger impact in grade 2 than grade 1, a larger impact in nongovernment schools than public schools, and smaller outcomes in mathematics than for English or Kiswahili. These ﬁndings have relevant policy implications in Kenya given an impending national mathematics programme.
shortDOI: 10/gftrqc KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2016.1149502 10/gftrqc 2339240:9H3B7D35 2339240:U483WVFF 2405685:J47PXP4U 2405685:SUWZCIEL
Keywords: Kenya; Numeracy; elementary school; instruction; international education; mathematics

The influence of infrastructure, training, content and communication on the success of NEPAD’S pilot e-Schools in Kenya - Nyagowa, Hesbon O; Ocholla, Dennis N; Mutula, Stephen M (Information Development, 2014)
This study was conducted to evaluate the contribution of four of the seven e-School dimensions to the success of the pilot phase of the New Partnership for Africa’s Development (NEPAD) e-School project in Kenya. The study employed survey research methodology. All six of the NEPAD e-Schools in Kenya were included and the teachers and students in those schools formed the study population. Of the 5,186 students and teachers, a representative sample of 1,508 was selected using probabilistic techniques. Data was collected using observations and a survey questionnaire. It was established that all six of the e-Schools had installed the basic computing facilities required for integrating information and communication technologies (ICT) in teaching and learning; all the e-Schools were observed to have the Very Small Aperture Terminal (VSAT) for Internet access in computer laboratories where a variable number of computers were installed. The ICT infrastructure provided modest communication capabilities. But while teachers received technical (ICT) training, they did not receive training on pedagogies for ICT integration in teaching and learning. We conducted hypothesis testing and confirmed that the four dimensions of E-School Success Model, investigated in the current study, positively contribute towards the success of the e-School. We therefore concluded that ICT infrastructure quality, content and communication quality, training effectiveness and use make considerable contributions to the success of the pilot phase of the NEPAD e-School project in Kenya. We recommend that stakeholders should continue investing in the NEPAD e-School project. Further studies on the impact of the other three dimensions of the e-Schools are recommended.
Sage UK: London, England shortDOI: 10/f6jwcp KerkoCite.ItemAlsoKnownAs: 10.1177/0266666913489698 10/f6jwcp 2339240:92BVGHM8 2405685:E6WWI998 2405685:NHIH8TRB
Keywords: Kenya; New Partnership for Africa’s Development; e-schools

2019 Kenya Population and Housing Census Volume IV: Distribution of Population by Socio-Economic Characteristics - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:NZQXRK6V 2405685:J4ZWA4L5

Kenya Population and Housing Census Results - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)
The total enumerated population was 47,564,296 Of which 23,548,056 were Males, 24,014,716 were Females and 1,524 were Intersex Females accounted for 50.5% of the total population The population has grown to 47.6 Million in 2019 from 37.7 Million in 2009 The intercensal growth rate has declined to 2.2% in 2019, from 2.9% in 2009 Average …
Library Catalog: www.knbs.or.ke Section: 2019 Census KerkoCite.ItemAlsoKnownAs: 2405685:5MHY2Y9G

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
shortDOI: 10/f7fghr KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 10/f7fghr 2405685:4WTUAF8V 2405685:USCCYKCK 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen (International Journal of Educational Development, 2016)
Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions – e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.
EdTechHub.Copy: 2129771:QHYYISLI shortDOI: 10/f8t8wn KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2016.03.006 10/f8t8wn 2129771:QHYYISLI 2339240:45CT95ZX 2339240:59F29QUS 2339240:AKA34H48 2339240:ERJRDYGR 2339240:JWWGS2FM 2339240:VHERHC8U 2339240:W2IRHE4N 2405685:6GPCWMKY 2405685:DH6QGZK3 2405685:DSJ268AF 2405685:HNU98RFR 2405685:NAH85KGQ 2405685:RJ64GDLT 2405685:T6BQBZK6 2405685:Y3YWXGDF 2534378:DA5UA4C3 2534378:IQ2QU9ZM 2534378:NFIYL9F6
Keywords: Education policy; International education; Kenya; Literacy; Reading; Technology; __:import:01; __:match:final; __:matched; __:study_id:2457283; ___working_potential_duplicate; __finaldtb

Multilingual Literacy Skill Development in Kenya: Results from Medium Scale Randomized Controlled Trials. - Piper, Benjamin (Society for Research on Educational Effectiveness, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:WUXXIKSF 2405685:BJJQHSKH
Keywords: ⛔ No DOI found

Developing a systemic approach to teacher education in sub-Saharan Africa: emerging lessons from Kenya, Tanzania and Uganda - Hardman, Frank; Ackers, Jim; Abrishamian, Niki; O’Sullivan, Margo (Compare: A Journal of Comparative and International Education, 2011)
While many countries in Eastern and Southern Africa are on track for meeting the Education for All targets, there is a growing recognition of the need to improve the quality of basic education and that a focus on pedagogy and its training implications needs to be at the heart of this commitment. By drawing on three East African countries, Kenya, Tanzania and Uganda, which are at different stages of development with regard to the reforming of teacher education, this paper explores the challenges and the lessons learned from each of the countries with regard to the development and strengthening of pre- and in-service training. The tension between quality, breadth and cost-effectiveness is explored together with a broader discussion of key principles to be taken into account when enhancing teacher education in the region as a whole.
shortDOI: 10/gftr63 KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2011.581014 10/gftr63 2339240:7KFNHLPK 2339240:I6BDIQNZ 2339240:JJ5GL8XB 2339240:LE5N7BCQ 2405685:CBBDLLFH 2405685:J57J3RGT 2405685:PDZKWSFZ 2405685:Q7GP9QSC 2405685:QWHDI7ZH 2534378:L9VFMLYK
Keywords: C:Kenya / Uganda / Tanzania; Education; Education for All; Education reform; Kenya; Pedagogy; Principles; Quality of education; Tanzania; Teacher education; Uganda; ___working_potential_duplicate; basic education; pre-service and in-service training; quality education; sub-Saharan Africa; teacher education reform

Technology adoption in secondary mathematics teaching in Kenya: An explanatory mixed methods study - Kamau, Leonard Mwathi (Syracuse University, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:THKYV7MT 2405685:IAYQII5V
Keywords: ⛔ No DOI found

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using Information and Communication Technology, 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya’s education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
KerkoCite.ItemAlsoKnownAs: 2339240:58E7TTX7 2339240:BKA9N5C4 2405685:3TIEJDV8 2405685:7L6V38N5 2405685:8NPF9AFB 2405685:IB7ASVMU 2534378:6WZ3BZFJ 2534378:A9KF6S9G 2534378:J2U5DHN3 2534378:QRRUK48B 2534378:WAL7Y23P 2534378:YIC9AUDV 2534378:ZPTKHLIH
Keywords: Accountability; C:Kenya; Classrooms; Clinical trials; Developing countries–LDCs; Digital divide; Digital literacy; ERIC; Current Index to Journals in Education (CIJE); Education; Education reform; Educational Practices; Educational Quality; Educational Technology; Educational technology; Foreign Countries; Handheld Devices; Initiatives; Intervention; Interviews; Kenya; Learning; Literacy; Literacy programs; Literature reviews; Maine; National Surveys; Observation; Outcomes of Education; Portugal; Quality; Questionnaires; Reading; Schools; Software; South Korea; Statistical Analysis; Statistical Significance; Students; Teachers; Teaching; Technology Uses in Education; Telecommunications; Texas; Turkey; Uruguay; __:import:01; __:match:final; __:matched; __:study_id:2096038; __finaldtb; ⛔ No DOI found

Teaching Practices in the 21st Century in Kenya: A Qualitative Approach - Kaume-Mwinzi, Regina K. (International Journal of Educational Excellence, 2018)
Education is an engine for the growth and progress of any society and it is responsible for building human capital which sets technological and economic growth. In the pre-technology education context, the teacher controlled the instructional process, the content was delivered to the entire class and the teacher emphasized factual knowledge. However, the current global demands in education require the use of approaches that are learner-centered and embracing integration of ICT. The purpose of this study is to establish the pedagogy used in Kenya for the 21st century learner. The case study design was used to collect qualitative data from three teachers who were purposively sampled from three education sub-sectors in Kenya: primary, secondary and university. The interview was guided by three research questions: Which teaching practices are used in Kenya? Which are the ‘best’ teaching practices in Kenya in the 21st century? What are the barriers for the ‘best’ teaching practices in Kenya? The findings were that the teaching methods currently in use were mainly teacher-centered although the respondents revealed that the ‘best’ teaching practices for the 21st century learner were student-centered. However, the barriers were large classes, lack of resources and facilities among other factors. The study recommends realignment of education policies to give priority to build pedagogical capabilities of teachers, provide digital tools and other resources. This would enable the 21st century learners’ opportunity to unleash their potential.
KerkoCite.ItemAlsoKnownAs: 10.18562/ijee.034 10/ggjrhq 2339240:T76TEDIL 2405685:XJKPKRMP

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using Information and Communication Technology, 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya’s education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
KerkoCite.ItemAlsoKnownAs: 2339240:58E7TTX7 2339240:BKA9N5C4 2405685:3TIEJDV8 2405685:7L6V38N5 2405685:8NPF9AFB 2405685:IB7ASVMU 2534378:6WZ3BZFJ 2534378:A9KF6S9G 2534378:J2U5DHN3 2534378:QRRUK48B 2534378:WAL7Y23P 2534378:YIC9AUDV 2534378:ZPTKHLIH
Keywords: Accountability; C:Kenya; Classrooms; Clinical trials; Developing countries–LDCs; Digital divide; Digital literacy; ERIC; Current Index to Journals in Education (CIJE); Education; Education reform; Educational Practices; Educational Quality; Educational Technology; Educational technology; Foreign Countries; Handheld Devices; Initiatives; Intervention; Interviews; Kenya; Learning; Literacy; Literacy programs; Literature reviews; Maine; National Surveys; Observation; Outcomes of Education; Portugal; Quality; Questionnaires; Reading; Schools; Software; South Korea; Statistical Analysis; Statistical Significance; Students; Teachers; Teaching; Technology Uses in Education; Telecommunications; Texas; Turkey; Uruguay; __:import:01; __:match:final; __:matched; __:study_id:2096038; __finaldtb; ⛔ No DOI found

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Kibukho, K.; Kwayumba, Dunston; Jepkemei, Evelyn; Piper, Benjamin (2014)
Kenya is investing in information and communication technology (ICT) to improve children’s learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students.
Publisher: RTI International. P.O. Box 12194, Research Triangle Park, NC 27709-2194. Tel: 919-541-6000; e-mail: publications@rit.org; Web site: http://www.rti.org KerkoCite.ItemAlsoKnownAs: 2339240:WXEI8ABZ 2405685:MJ9ENT2D
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Kenya Overview - World Bank (2019)
The World Bank’s work in Kenya supports the government’s Vision 2030 development strategy, which aims to accelerate sustainable growth, reduce inequality, and manage resource scarcity.
Library Catalog: www.worldbank.org KerkoCite.ItemAlsoKnownAs: 2405685:3KINEYR6

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a National Education System - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using ICT, 2017)
Previous large-scale education technology interventions have shown only modest results. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed a national tablets program. The program provides tablets to each of more than 1200 instructional coaches in the country and includes a national database of classroom quality, which is used by the education system to monitor education quality. The tablets program helps coaches to...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:AM3KBAP6 2405685:UKTDQWEN
Keywords: ⛔ No DOI found

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a National Education System - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using ICT, 2017)
Previous large-scale education technology interventions have shown only modest results. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed a national tablets program. The program provides tablets to each of more than 1200 instructional coaches in the country and includes a national database of classroom quality, which is used by the education system to monitor education quality. The tablets program helps coaches to...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2405685:R3U2G3YM 2486141:5ZICUTPI
Keywords: ⛔ No DOI found

Improving Early-Grade Literacy in East Africa: Experimental Evidence from Kenya and Uganda - Lucas, Adrienne M.; McEwan, Patrick J.; Ngware, Moses; Oketch, Moses (Journal of Policy Analysis and Management, 2014)
Primary school enrollments have increased rapidly in sub-Saharan Africa, spurring concerns about low levels of learning. We analyze field experiments in Kenya and Uganda that assessed whether the Reading to Learn intervention, implemented by the Aga Khan Foundation in both countries, improved early-grade literacy as measured by common assessments. We find that Ugandan literacy (in Lango) increased by 0.2 standard deviations. We find a smaller effect (0.08) on a Swahili literacy test in Kenya. We find no evidence that differential effects are explained by baseline differences across countries in student test scores, classroom attributes, or implementation fidelity. A plausible explanation that cannot be directly tested is differential effective exposure to the literacy treatment in the tested languages. Students in Kenya were tested in Swahili, which is not necessarily the main language of instruction in primary schools, despite official policy.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pam.21782 shortDOI: 10/gf7gt2 KerkoCite.ItemAlsoKnownAs: 10.1002/pam.21782 10/gf7gt2 2405685:6XBY922E

E-learning in secondary Schools in Kenya: A Case of the NEPAD E-schools - Ayere, Mildred; Odera, F; Agak, John (Educational Research and Reviews, 2010)
The New Partnership for Africa's Development (NEPAD) schools were set up as centres of excellence in Information and Communication Technology (ICT) integration, so that other schools could copy their model in e-learning. It was for this reason that they were provided with computers, e-materials, internet appliances and trained personnel. But to gauge their levels of success as e-learning centres there was need to compare them to other schools offering ICT education in Kenya. It was for this reason that this study compared the application of the e-learning in NEPAD and non-NEPAD schools in Kenya. Specifically, the study: Identified significant differences in levels of integration of ICT in curriculum subjects; surveyed the differences in use of e-materials in education research; examined availability of e-libraries; identified significant differences in academic performance of NEPAD and non-NEPAD schools attributed to e-learning. The study used a combination of an exploratory approach using descriptive survey and ex-post-facto design. It was carried out in six of the eight provinces in Kenya, where the NEPAD schools are located. It targeted 1600 form four students from 35 secondary schools involved in ICT education (NEPAD schools included). Saturated sampling was used for the six NEPAD schools while six non-NEPAD schools were selected through simple random sampling. The sample consisted of three officials from the ministry of education, twelve principals and twelve heads of ICT department (HODs), and 570 of the form four students. The main data collection instrument was the questionnaire; administered to the students, the principals, and the HODs. The interview schedule was administered to the ministry of education personnel while an observation checklist was used as a confirmatory tool. Analysis was done using both descriptive and inferential statistics. The study found that, there was a significant difference in the application of e-learning in NEPAD and non-NEPAD schools. Based on these findings, it was recommended that schools involved in ICT education should intensify teacher facilitation and support teacher roles that are required in e-learning Key words: E-Learning, ICT integration, ICT education, new partnership for Africa's development (NEPAD).
KerkoCite.ItemAlsoKnownAs: 2339240:2UFRZUA4 2405685:C5RVGKXP
Keywords: ⛔ No DOI found

Integration of ICT in Education in a Secondary School in Kenya: A Case Study - Kisirkoi, Florence (Literacy Information and Computer Education Journal, 2015)
Amidst reports that there was very little integration of Communication Information Technology (ICT) in curriculum delivery in many secondary schools in Kenya, it was reported that one secondary school was using ICT in instruction and practicing learner centered instructional approaches and there was improved learning outcomes. The school’s mean score in the Kenya Certificate of Secondary Education had improved from 6.2 to 8.4 between 2007 and 2013. This study teacher computer literacy levels, motivation for integration, perceived reason for the intervention and the impact on teaching and learning. A case study was conducted and observation and interview schedules were used to collect data. The study population was the 535 students and the 28 teachers in the school. Simple random sampling was used to sample 30 students and 18 teachers. It was established that the students and teachers were computer literate and were able to manage computer applications for teaching and learning. The Learning process was found to be practical with learner interactions and activities based learning. The motivation was desire to teach better coupled with visionary, supportive school leadership. The school was using ICT as teaching learning tool and there was improvement of learning environment and outcomes. Many schools ought to emulate the school.
KerkoCite.ItemAlsoKnownAs: 10.20533/licej.2040.2589.2015.0253 10/gj37fv 2339240:79CQYH29 2405685:BV3P33XH

Computerizing Primary Schools in Rural Kenya: Outstanding Challenges and Possible Solutions - Ogembo, Javier Gordon; Ngugi, Benjamin; Pelowski, Matthew (The Electronic Journal of Information Systems in Developing Countries, 2012)
This paper investigates the outstanding challenges facing primary schools’ computerization in rural Kenya. Computerization of schools is often envisaged as a ‘magic’, or at least a particularly efficient, solution to many of the problems that developing countries face in improving primary school education. However, while a great deal of consideration is given to the technical issues surrounding computer implementation, government policy makers, administrators, aid organizations and individuals participating in school computerization programs often have not carefully considered the contextual questions surrounding this endeavour. Specifically: 1.) what problems do rural schools actually want to solve with computerization; 2.) is computerization the most important priority for rural schools; 3.) are schools ready, in terms of infrastructure, for a computer in the classroom; or 4.) might there be better avenues for implementing access to the benefits of the digital age? These questions and the issue of school computerization are considered via results from a survey of thirty-seven rural Kenyan primary public schools. Results indicate that, while all schools had low ICT status making them primary targets for computerization, only eleven percent had at least one ICT compliant teacher, of which all were considered to require further training. In addition we found inadequate infrastructural preparedness – lack of access to electricity, internet; no classroom computer space, few desks, secure walls and protective roofing – posing severe challenges to the outstanding conception of computerization. We consider these results and make recommendations for better adapting programs for computer introduction, and also suggest the use of new innovative devices, such as cell phones, which might already have overcome many of the technical challenges found.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/j.1681-4835.2012.tb00371.x KerkoCite.ItemAlsoKnownAs: 10.1002/j.1681-4835.2012.tb00371.x 10/gf7gs8 2339240:33SJHXL4 2405685:NMZU3HHJ
Keywords: ICT; cell phone; classrooms; computerization; primary schools; techno-literacy

Designing for Scale: Reflections on Rolling Out Reading Improvement in Kenya and Liberia - Gove, Amber; Poole, Medina Korda; Piper, Benjamin (New Directions for Child and Adolescent Development, 2017)
Since 2008, the Ministries of Education in Liberia and Kenya have undertaken transitions from small-scale pilot programs to improve reading outcomes among primary learners to the large-scale implementation of reading interventions. The effects of the pilots on learning outcomes were significant, but questions remained regarding whether such large gains could be sustained at scale. In this article, the authors dissect the Liberian and Kenyan experiences with implementing large-scale reading programs, documenting the critical components and conditions of the program designs that affected the likelihood of successfully transitioning from pilot to scale. They also review the design, deployment, and effectiveness of each pilot program and the scale, design, duration, enabling conditions, and initial effectiveness results of the scaled programs in each country. The implications of these results for the design of both pilot and large-scale reading programs are discussed in light of the experiences of both the Liberian and Kenyan programs.
shortDOI: 10/ggkzrw KerkoCite.ItemAlsoKnownAs: 10.1002/cad.20195 10/ggkzrw 2405685:HTRYQVPL

Status of Teachers' Technology Uptake and Use of GeoGebra in Teaching Secondary School Mathematics in Kenya - Mwingirwa, Irene Mukiri; Marguerite, Miheso Khakasa (International Journal of Research in Education and Science, 2016)
The uptake of technology and specifically, GeoGebra software, in teaching mathematics has had mixed success in spite of its documented benefits. This study investigated teachers’ perspective towards training and eventual use of GeoGebra as a tool to enhance learning of mathematics. In this article we share findings from a larger study that was conducted in Kajiado County in Kenya (Africa) on GeoGebra use in teaching Secondary School Mathematics. This article presents the relationship between observed teachers’ perceptions towards the uptake of GeoGebra, a technology based tool and the actual uptake of GeoGebra using the Diffusion Innovation theoretical framework. Data was collected from practicing mathematics teachers who were exposed to GeoGebra through a series of training sessions. The findings after training sessions with the mathematics teachers showed willingness to use GeoGebra in their classes. The teachers identified Geometry as the topic where use of GeoGebra would be most relevant due to its abstract nature. Teachers’ responses indicated that GeoGebra was perceived as useful for teaching and learning Mathematics and that it would help learners grasp concepts in Geometry. However, the study also found out that systemic support would sustain teachers’ engagement with GeoGebra at classroom level as actualization of Geogebra use did differ significantly from teachers’ perceptions.
shortDOI: 10/gf5f55 KerkoCite.ItemAlsoKnownAs: 10.21890/ijres.83989 10/gf5f55 2339240:KK6SERL3 2405685:NLT9DE96

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
shortDOI: 10/gf6298 KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-018-9325-4 10/gf6298 2339240:HUMPM4BM 2339240:LT7INWTK 2339240:PM36I7JC 2339240:S7I52VEN 2339240:YTWJW5GH 2405685:2YJ8XQDL 2405685:NC6R6NWC 2405685:TFDLRYCG 2405685:UXBBCZIX 2405685:VERKPHLS 2405685:X7T5JCV4
Keywords: ___working_potential_duplicate

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=108296506&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 2339240:B8GCJR9U 2405685:7W777384 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Determinants of Implementation of Public Sector Projects in Kenya: A Case of Laptop Project in Public Primary Schools in Kangundo Sub-County, Machakos County - Muinde, Samuel Mutisya; Mbataru, Patrick (2019)
In One-to-one laptop programs are becoming popular across the globe. However available evidence suggests that their implementations in schools are often faced with challenges. For example, even though the government of Kenya began supplying laptops to public primary schools in 2016; reports indicate that the gadgets have not fully been put into use in many schools. Most of the empirical studies done in this area have majorly focused on the level of success and factors influencing implementation of the project and not the extent to which specific variables determine implementation of the project, thus resulting to a research gap. In order to fill this gap, study focused on the determinants of implementation of the laptop project in public primary schools in Kangundo Sub-county. The study was guided by 4 research objectives: i.) To assess the extent to which teachers’ perception determine implementation of the laptop project; ii) To establish the extent to which teachers’ capacity in ICT determine implementation of the laptop project; iii) To establish the extent to which availability of facilities determine the implementation of the laptop project; and iv) To establish the extent to which availability of digital subject content determine implementation of the laptop project. The study was premised on three (3) theories; Technology Acceptance Model, Constructivist Learning Theory and Resource Based Theory. The study adopted descriptive survey design. It targeted all the public primary schools, all teachers in lower primary and all the Ministry of Education officials heading the four zones that constitute Kangundo Sub-county. The study targeted all the 74 public primary schools which have 222 lower primary teachers, 74 head teachers and 4 MOEST officials making a total target population of 300. It adopted stratified random sampling in stratifying the schools into four zones and randomly selected 22 schools. All 22 school heads and all 66 lower primary school teachers of the participating schools were purposively sampled. Additionally, the 4 MOEST officials heading the four zones were included, making a sample of 92 participants. Tools of data collection included questionnaires for teachers and school heads, an interview guide for MOEST officials and an observation checklist. The data analysis was conducted using SPSS. Content analysis was adopted in analyzing qualitative data whereas descriptive statistics such as frequencies and percentages were used in analyzing quantitative data. Tables and figures were used to present the study results. The inferential analysis conducted shows that there was a significant relationship between independent and dependent variables. Both teachers’ capacity on ICT and availability of facilities were found to have significant effect on implementation of the laptop project while teachers’ perception and availability of digital subject content were found to have insignificant effect on the project in public primary schools in Kangundo Sub-County.
Accepted: 2020-06-30T09:17:59Z Publisher: International Academic Journal of Law and Society KerkoCite.ItemAlsoKnownAs: 2339240:2GJGUH3T 2405685:BVJFPMCV
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Digital Economy Blueprint - Kenya Digital Economy (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:6CTY84PQ

National Education Sector Strategic Plan - Ministry of Education, Kenya (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:MH6HTIBF

Digital Learning Programme - Ministry of Education, Kenya (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:IP7DIJBT

Second Quarter Statistics Report for the Financial Year 2019/2020 - Communications Authority of Kenya (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:3QABM8GW

National Education Sector Strategic Plan v2 - Ministry of Education, Kenya (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:K364JWL8

National Pre-primary Education Policy Standard Guidelines - Republic of Kenya Ministry of Education (Republic of Kenya Ministry of Education, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:2Z8TGS6P 2405685:C35JRU97

National Pre-Primary Education Policy 2017 - Republic of Kenya Ministry of Education (Republic of Kenya Ministry of Education, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:6B9E6N5V 2405685:AE5QA6PC

School-cooperation Kenya - Norway: friendship and learning through social media? - Pedersen, Hege (86 s., 2015)
Accepted: 2015-03-05T11:59:13Z KerkoCite.ItemAlsoKnownAs: 2339240:PRIMQ47B 2405685:P6RCUCY9
Keywords: ⛔ No DOI found

National Information, Communications and Technology (ICT) Policy - Ministry of Information, Communications and Technology, Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:3MTGT25S

Kenya National Education Sector Strategic Plan 2018 - 2022 - Ministry of Education, Republic of Kenya (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:56YDNKHI 2405685:8I8K8B9A

Home - Ministry of Education, Kenya (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:PKXCNKUD

Kenya Broadcasting Corporation (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:RYQDKX8X

Telkom Kenya Limited (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:N3EXUGKG

Kenya Publishers Association (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:9A5R6KAC

Kenya National Examination Council (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:LVGWP5NJ

Elimika (Kenya Education Cloud) (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:D4BCHAZW 2405685:ISBJKG3V

Inequalities in Human Development in the 21st Century, Kenya - UNDP (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:392IVFST

Reading Skill Transfer across Languages: Outcomes from Longitudinal Bilingual Randomized Control Trials in Kenya and Haiti. - Piper, Benjamin; Bulat, Jennae; Johnston, Andrew (Society for Research on Educational Effectiveness, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:VTSTD8ZH 2405685:N8H5282W
Keywords: ⛔ No DOI found

GPE 2020 Country-level Prospective Evaluations: First annual Report Kenya - Rawal, Prepared Shenila; Aslam, Monazza; Outhred, Rachel (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:XN28CFK6
Keywords: ⛔ No DOI found

USAID/Kenya Primary Math and Reading (PRIMR) Initiative: Kisumu Information and Communication Technology (ICT) Intervention. Endline Report. - Piper, B.; Kwayumba, D. (Research Triangle Institute (RTI), 2014)
00000 KerkoCite.ItemAlsoKnownAs: 2129771:ILKMBDCW 2405685:7K6TGAXF

Examining the secondary effects of mother-tongue literacy instruction in Kenya: Impacts on student learning in English, Kiswahili, and mathematics - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Oyanga, Arbogast (International Journal of Educational Development, 2018)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2017.10.002 2405685:RN8DGSVY 4042040:BQCK8KIK

M-Shule - Together we learn, together we succeed - M-Schule LTd (2018)
M-Shule is the first adaptive, mobile learning management platform designed to improve performance for millions of primary school students across Kenya and Sub-Saharan Africa
Library Catalog: m-shule.com KerkoCite.ItemAlsoKnownAs: 2405685:SBPUP4HV

A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine (Distance Education, 2018)
The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.
shortDOI: 10/ggdcng KerkoCite.ItemAlsoKnownAs: 10.1080/01587919.2018.1429896 10/ggdcng 2339240:FKXTDETC 2405685:XWRSN3WD
Keywords: Re-entry; dropouts; open distance e-learning

Learning English Language by Radio in Primary Schools in Kenya - Odera, Florence (2011)
Learning English Language by Radio in Primary Schools in Kenya By Florence Y. Odera (PhD) P.O.Box 2303, Kisumu, Kenya Introduction and background information One of the
KerkoCite.ItemAlsoKnownAs: 2339240:H2WW7AHK 2405685:AI2IS3MP
Keywords: ___working_potential_duplicate

Experimental evidence on scaling up education reforms in Kenya - Bold, Tessa; Kimenyi, Mwangi; Mwabu, Germano; Ng’ang’a, Alice; Sandefur, Justin (Journal of Public Economics, 2018)
What constraints arise when translating successful NGO programs to improve public services in developing countries into government policy? We report on a randomized trial embedded within a nationwide reform of teacher hiring in Kenyan government primary schools. New teachers offered a fixed-term contract by an international NGO significantly raised student test scores, while teachers offered identical contracts by the Kenyan government produced zero impact. Observable differences in teacher characteristics explain little of this gap. Instead, data suggests that bureaucratic and political opposition to the contract reform led to implementation delays and a differential interpretation of identical contract terms. Additionally, contract features that produced larger learning gains in both the NGO and government treatment arms were not adopted by the government outside of the experimental sample.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jpubeco.2018.08.007 2339240:58EIIZ3H 2405685:XRHDAKJR 4656463:B7GSKCJK
Keywords: Contract teachers; Education; External validity; Kenya; Randomized evaluation; State capacity

Tusome Early Grade Reading Activity - RTI International (RTI, 2016)
Across Kenya, literacy rates in primary schools are significantly lower than expected despite increased access and enrollment. The Kenyan education system is seeking to improve learning outcomes by instilling better instructional practices, expanding resources for teacher training, and developing learning materials that support multilingual literacy. Kenya’s approach to the challenge of raising literacy and learning outcomes is unique in its ambitious goals and well-researched methods for achieving its goal at a national scale.
Library Catalog: www.rti.org KerkoCite.ItemAlsoKnownAs: 2339240:XNM3FD3A 2405685:GEG6RSZ3 2405685:NNFW4F3L GEG6RSZ3

PARENTAL INVOLVEMENT IN PRIMARY SCHOOLS IN KENYA AS A MAJOR STRATEGY FOR ACADEMIC SUCCESS - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
The new Kenyan curriculum emphasizes the role of parents as essential to their children’s education and in the success of curriculum implementation. The development requires a change in how parents and the community interact with schools and education. The perception in Kenya has always been that education is the sole responsibility of the school and the teacher. And so, parental involvement in Kenya has mainly been limited to financial contributions and teacher-parent meetings. With the introduction of new curriculum, the role of parent is crucial for the academic success of the child. A literature study investigated the extent of parental involvement in primary schools in Kenya. The data is obtained from a variety of library articles addressing parental involvement in Primary schools in different counties in Kenya. The current study found that majority of parents are involved in their children’s education, however, more awareness of the parental involvement is needed and more strategies on parental involvement needs to be employed for the success of the new curriculum. Article visualizations:
Number: 0 KerkoCite.ItemAlsoKnownAs: 10.46827/ejes.v0i0.2011 2405685:H59Q6NHX
Keywords: academic achievement; parental involvement; primary schools; ⚠️ Invalid DOI

PARENTAL INVOLVEMENT IN PRIMARY SCHOOLS IN KENYA AS A MAJOR STRATEGY FOR ACADEMIC SUCCESS - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
The new Kenyan curriculum emphasizes the role of parents as essential to their children’s education and in the success of curriculum implementation. The development requires a change in how parents and the community interact with schools and education. The perception in Kenya has always been that education is the sole responsibility of the school and the teacher. And so, parental involvement in Kenya has mainly been limited to financial contributions and teacher-parent meetings. With the introduction of new curriculum, the role of parent is crucial for the academic success of the child. A literature study investigated the extent of parental involvement in primary schools in Kenya. The data is obtained from a variety of library articles addressing parental involvement in Primary schools in different counties in Kenya. The current study found that majority of parents are involved in their children’s education, however, more awareness of the parental involvement is needed and more strategies on parental involvement needs to be employed for the success of the new curriculum. Article visualizations:
Number: 0 KerkoCite.ItemAlsoKnownAs: 10.46827/ejes.v0i0.2011 2405685:H59Q6NHX
Keywords: academic achievement; parental involvement; primary schools; ⚠️ Invalid DOI

Factors Affecting Adoption of E-Learning Technology in Kenya - Kingori, Rhoda Mbithe (United States International University - Africa, 2018)
Internet penetration in Africa has been accelerated, with Kenya at the fore front at over 89.5% penetration, this penetration has led to an increase in knowledge repository for Kenyans to choose from and as a result E-learning has steadily increased not only in tertiary institutions but in informal learning as well. Facebook and YouTube are some of the web based tools, – that are listed as having potential applications for teaching and learning. As a result, it is essential to understand the challenges faced in the adoption of e-learning technology. The overall purpose of this study was to investigate the factors affecting adoption of e-learning technology in Kenya with a focus on three key factors, self-efficacy, objective usability and system accessibility. This study used explanatory/hypothesis research design to investigate the factors which affect adoption of e-learning technology in Kenya. An explanatory research design was fit to the study because it will helped to ascertain not only the relationship between the different variables, but measure the effect and strength of each independent variable on the dependent variable which was the technology adoption. The target population was social media (Facebook) users in Kenya. According to Internet World Statistics there are over 6.2 million Facebook subscribers in Kenya as of June 2017. This study focused on 200 social media users in Nairobi who were interested in e-learning or have ever learned online. They were sampled by geographic cluster, simple random sampling technique with a focus on Nairobi. Online questionnaire was used by Google form and 93% responded. In the first objective of self-efficacy, the correlation result revealed positive correlation between perceived ease of use with self-efficacy (r=0.441, p<0.05) and perceived usefulness with self-efficacy(r=0.337, p<0.05). On the CFA, there was a strong model equation but on the SEM it was not. The path coefficient for the relationship between SE and adoption of e-learning was weak. In the second objective, the correlation result revealed positive correlation between perceived ease of use with objective usability (r=0.598, p<0.05) and perceived usefulness with SE (r=0.456, p<0.05). Based on SEM, the path coefficient for the relationship between objective usability and adoption of e-learning was significant. Without any latent/intervening variable, OU and PEOU was positive and significant at the 0.05 level (βeta=0.938, T-value =3.658, p<0.05). The positive relationship indicates that one unit increase in OU will result in 0.938 increases in PEOU. In the last objective of system accessibility, the correlation result revealed positive correlation between perceived ease of use with system accessibility (r=0.441, p<0.503) and perceived usefulness with system accessibility (r=0.514, p<0.05). The path coefficient for the relationship between system accessibility and adoption of e-learning was weak and not significant hence dropped from the model.The research established that Self-efficacy had little to no effect on adoption of e-learning technology in Kenya. Objective usability was the strongest factor affecting the adoption of e-learning technology while system accessibility had correlation but was not strong enough to impact the model and as such impact the adoption of e-learning technology in Kenya was weak. These findings provided some useful insights for governments, potential instructors or educators, e-learning platforms and policy makers. This recommends and highlights the need to shift from the metropolitan areas to the rural areas in order to get a holistic view of the e-learning environment in Kenya. This research shed light on objective usability as a strong factor on perceived ease of use and perceived usefulness and as such on the adoption of e-learning technology in Kenya. Based the responses received and the SEM analysis further research should focus on the two variables of system accessibility and self-efficacy involving a larger number of variables to examine, as well as larger numbers of respondents to support the factor analysis. Research should also focus on attitude and behavioral intention and their interaction with perceived eases of use and perceived usefulness. The research needs to now shift from the metropolitan areas to the rural areas in order to get a holistic view of the e-learning environment in Kenya.
Accepted: 2019-02-06T07:09:51Z KerkoCite.ItemAlsoKnownAs: 2339240:PM78VDNA 2405685:F9AKUAFD

Spatial models for the rational allocation of routinely distributed bed nets to public health facilities in Western Kenya - Macharia, Peter M.; Odera, Patroba A.; Snow, Robert W.; Noor, Abdisalan M. (Malaria Journal, 2017)
In high to moderate malaria transmission areas of Kenya, long-lasting insecticidal nets (LLINs) are provided free of charge to pregnant women and infants during routine antenatal care (ANC) and immunization respectively. Quantities of LLINs distributed to clinics are quantified based on a combination of monthly consumption data and population size of target counties. However, this approach has been shown to lead to stock-outs in targeted clinics. In this study, a novel LLINs need quantification approach for clinics in the routine distribution system was developed. The estimated need was then compared to the actual allocation to identify potential areas of LLIN over- or under-allocation in the high malaria transmission areas of Western Kenya.
KerkoCite.ItemAlsoKnownAs: 10.1186/s12936-017-2009-3 2405685:VQJ4C4KI 4042040:FC3UL7UT
Keywords: ANC utilization; Equity; LLINs allocation; Spatial modelling

Challenges Facing Adoption of Information Communication Technology (ICT) In Educational Management in Schools in Kenya - Kipsoi, Emmy; Chang'ach, Dr; Sang C, Hellen (Journal of Sociological Research, 2012)
ICT has contributed greatly to educational management in schools globally (Zhao and Frank, 2003). However, in Kenya schools hardly use ICTs to manage the quality of output, or to raise teacher productivity, or to reduce costs through analyzing spending. This is attributed to a myriad of challenges facing most schools in Kenya with regard to adoption of ICTs in educational management. This has resulted to a slow rate of adoption of technology despite its promise and potential for use in educational management in schools. As such, this paper analyses the lethargy that has surrounded education management in schools with respect to acquisition of Information Communication Technology. Education and training sector has a major role to play in the implementation of the proposed ICT policy. First, the sector itself is a major user of ICT, not only in education, training and research but also in the management of the sector. The paper argues that ICT policies must be dynamic, cost-effective, adaptable, and differentiated between sectors and between the various segments of educational management in order to contribute effectively to education management. The recommendations of this paper provide a basis for the urgent need for the integration of ICTs in educational management in schools in Kenya.
KerkoCite.ItemAlsoKnownAs: 10.5296/jsr.v3i1.1882 2339240:RXCIEA2R 2405685:EMUX9EK9

An E-Learning Approach to Secondary School Education”: E-Readiness Implications in Kenya - Redempta, Kiilu (Journal of Education and Practice, 2012)
Information and Communication Technology (ICT) has the potential to enhance access, quality, and effectiveness in education. This paper examines the E-readiness implication on the adoption of e-learning in secondary schools in Kenya. The paper provides an opportunity for reflection on e-learning adoption and the potential role ICT can plays in education. The review has established that up to date, less than 10% of secondary schools in Kenya offer computer studies as a subject in the curriculum despite its perceived potential. The few schools that have an ICT programme limit the number of candidates who take up the subject considering it a specialty irrespective its being an essential subject as other compulsory subjects like Mathematics and Languages. Whereas the processing of information to build knowledge is one of the essential literacy skills vital for the workforce in the 21st century, it is often overlooked in current educational practices. the question of ereadiness of Kenyan schools cannot be overlooked if Kenya plans to use education as a platform for becoming an e-society of the 21st century as envisaged in Vision 2030.Therefore, it is imperative that E-Readiness issues be effectively addressed lest new technology introduced further marginalizes the already deprived Kenyan children. Desktop review of relevant literature was guided by Current Situation Analysis (CSA) which is equivalent to Strength, Weakness, Opportunities and Threats (SWOT) Analysis.
KerkoCite.ItemAlsoKnownAs: 2339240:QGAYFNJL 2405685:74DSLY4X
Keywords: ⛔ No DOI found

National Information, Communications and Technology (ICT) Policy - Ministry of Information, Communications and Technology, Kenya (Government of Kenya, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:P4P4HDNQ 2405685:DZ2QSTVI

The County Allocation of Revenue Bill, 2019 - Government of Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:HBM87LKU

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-018-9325-4 10/gf6298 2339240:3W37ZTWQ 2405685:ME5VHAM9
Keywords: ___working_potential_duplicate

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-018-9325-4 2339240:X8L2E7PR 2405685:TQU6RKR4
Keywords: Evaluation; Implementation; Literacy; National; Reading; Reform; Systems

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1179/003962611X13117748892155 KerkoCite.ItemAlsoKnownAs: 10.1179/003962611X13117748892155 2405685:HH3GP4V2 4042040:NJ6E8C3M
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

She called, she Googled, she knew: girls' secondary education, interrupted school attendance, and educational use of mobile phones in Nairobi - Zelezny-Green, Ronda (Gender & Development, 2014)
Girls in Kenya commonly face multiple barriers to school attendance. At the same time, mobile phone use is growing throughout the country, and particularly in urban centres including Nairobi. As this technology spreads, the possibility increases of people using mobile phones for their own development purposes, including for education and learning. This article examines mobile phone use by girls at one secondary school in Nairobi, and in particular their attempts to mediate interrupted school attendance using this technology.
Publisher: Routledge _eprint: https://doi.org/10.1080/13552074.2014.889338 shortDOI: 10/ggtsmq KerkoCite.ItemAlsoKnownAs: 10.1080/13552074.2014.889338 10/ggtsmq 2405685:BB3X32QY
Keywords: ICT4D; Kenya; ___working_potential_duplicate; gender; girls' education; international education and development; mobile learning; school attendance

The Effect of Computer-Assisted Instruction on Student’s Attitudes and Achievement in Matrices and Transformations in Secondary Schools in Uasin Gishu District, Kenya - Mwei, Philip K.; Too, Jackson K.; Wando, Dave (2011)
Performance in Mathematics in secondary school Education in Kenya remains poor. Consequently the Kenya secondary school examination (KCSE) Mathematics results continue to cause concern to all the stakeholders in the education sector. Therefore, there is serious and urgent need for intervention. Although research has indicated that computer-assisted instruction (CAI) enhances student achievement, promotes positive attitudes towards Mathematics and instruction, and improves interpersonal relations, few studies have focused on CAI in Kenyan secondary schools Mathematics teaching/learning. The purpose of this study was to investigate the effects of CAI on students’ attitude and achievement in matrices and transformations between form four students who received instruction using CAI module or conventional instruction methods. The pretest – posttest control group experimental research design was used. Six classes selected at random with 205 students participated in the study. Results of this study indicated higher achievement and positive attitudes with CAI treatment groups. Making connections between the goals of Mathematics education and CAI offers a valuable means for improving mathematical knowledge and skills and hence performance in Mathematics.
Accepted: 2020-04-29T08:24:24Z Publisher: World Council for Curriculum Instruction KerkoCite.ItemAlsoKnownAs: 2339240:6I5FF3K4 2405685:6SE7SU4R
Keywords: ⛔ No DOI found

Take advantage of demographic dividend - Kibaru-Mbae, Josephine; Chatterjee, Siddharth (UNFPA Kenya, 2016)
Kenya is at the cusp of a “demographic dividend” that could change the country’s fortunes in the first half of the 21st century, but only if the country takes the right steps towards investing in its youth.
KerkoCite.ItemAlsoKnownAs: 2339240:R986QUPX 2405685:6JJ9FYYB

Does community involvement affect teacher effort? Assessing learning impacts of Free Primary Education in Kenya - Atuhurra, Julius F. (International Journal of Educational Development, 2016)
While the impressive school participation impacts of Universal Primary Education policies in Sub-Saharan Africa are widely recognized, attempts to measure learning gains from schooling remain minimal. Utilizing a unique international test score dataset, we measure and explain grade six reading and math learning outcomes in Kenya. By comparing competences between public and private schools before and after the introduction of free primary education, we find large achievement declines and inequalities based on gender and socioeconomic status. The declines are associated with low teacher efforts and community disengagement. Policy studies on community involvement in schools will likely lead to improved learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2016.03.008 2339240:G3NSWQKR 2405685:MBZJNJH3
Keywords: Community involvement; Educational policy; Learning achievement; Teacher effort

Integrating Information Communication Technology Skills in Preschool Education in Kenya - Kaindio, Mauta; Wagithunu, Margaret (Mediterranean Journal of Social Sciences, 2014)
The study aimed at investigating the preparedness and attitude of ECDE teachers in preschools, and find out the current situation as far as ICT is concerned. The researchers adopted descriptive design. To obtain information on the current status of the ICT on whether there was any significant difference in preschool teachers’ preparedness in terms of age, qualifications, and experience on ICT. 52 preschool teachers were randomly selected and a questionnaire administered to them. The data was analyzed using SPSS computer software. It was clear from the finding that Kenya is not ready to integrate ICT in preschool curriculum, since the physical facilities, electricity, poverty, trained personnel and teachers’ attitudes towards ICT need to be addresses first. DOI: 10.5901/mjss.2014.v5n5p89
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2014.v5n5p89 10/gj37hc 2339240:IKPDXNHI 2405685:ZHP6QFFE

Integrating information communication technology skills in Preschool Education in Kenya - Kaindio, M.P.; Wagithunu, M.N. (Mediterranean Journal of Social Sciences, 2014)
The study aimed at investigating the preparedness and attitude of ECDE teachers in preschools, and find out the current situation as far as ICT is concerned. The researchers adopted descriptive design. To obtain information on the current status of the ICT on whether there was any significant difference in preschool teachers' preparedness in terms of age, qualifications, and experience on ICT. 52 preschool teachers were randomly selected and a questionnaire administered to them. The data was analyzed using SPSS computer software. It was clear from the finding that Kenya is not ready to integrate ICT in preschool curriculum, since the physical facilities, electricity, poverty, trained personnel and teachers' attitudes towards ICT need to be addresses first.
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2014.v5n5p 2339240:XS6MU4U5 2405685:EEPP4SFL
Keywords: ⚠️ Invalid DOI

Peer Effects, Teacher Incentives, and the Impact of Tracking: Evidence from a Randomized Evaluation in Kenya - Duflo, Esther; Dupas, Pascaline; Kremer, Michael (American Economic Review, 2011)
To the extent that students benefit from high-achieving peers, tracking will help strong students and hurt weak ones. However, all students may benefit if tracking allows teachers to better tailor their instruction level. Lower-achieving pupils are particularly likely to benefit from tracking when teachers have incentives to teach to the top of the distribution. We propose a simple model nesting these effects and test its implications in a randomized tracking experiment conducted with 121 primary schools in Kenya. While the direct effect of high-achieving peers is positive, tracking benefited lower-achieving pupils indirectly by allowing teachers to teach to their level. (JEL I21, J45, O15)
KerkoCite.ItemAlsoKnownAs: 10.1257/aer.101.5.1739 2339240:W5VT6F6A 2405685:98PTSC94
Keywords: Analysis of Education; Public Sector Labor Markets; Economic Development: Human Resources; Human Development; Income Distribution; Migration

She called, she Googled, she knew: Girls' secondary education, interrupted school attendance, and educational use of mobile phones in Nairobi - Zelezny-Green, Ronda (Gender & Development, 2014)
Girls in Kenya commonly face multiple barriers to school attendance. At the same time, mobile phone use is growing throughout the country, and particularly in urban centres including Nairobi. As this technology spreads, the possibility increases of people using mobile phones for their own development purposes, including for education and learning. This article examines mobile phone use by girls at one secondary school in Nairobi, and in particular their attempts to mediate interrupted school attendance using this technology.
17 citations (Crossref) [2024-02-28] Publisher: Routledge _eprint: https://doi.org/10.1080/13552074.2014.889338 KerkoCite.ItemAlsoKnownAs: 10.1080/13552074.2014.889338 2339240:6CUN627D 2405685:CYKZGKP3
Keywords: ICT4D; Kenya; gender; girls' education; international education and development; mobile learning; school attendance; ⛔ No INSPIRE recid found

Relationship between Teacher - Educator Characteristics and the Integration of Information and Communication Technologies in Teaching and Learning in Teacher Education Institutions in Kenya - Chemwei, B.; Kiboss, J.; Njag, Kageni (undefined, 2016)
It is a government policy that all institutions of learning in Kenya, across the curricula embrace Information Communication Technology (ICT) as the world moves towards knowledge based economy. The evidence in literature reveals positive effects of information and communication technology in instruction. But teachers have a challenging task in integrating the tools of ICT in teaching especially those teacher educators not quite exposed to technology. This is because so many factors influence ICT integration. In this paper, we explore the the relationship between teacher-educators’ age, gender, level of education, and teaching experience and the integration level of ICTs in teaching in primary teacher training colleges in Kenya. The simple random sampling technique was used to select six teacher training colleges in Kenya and 169 respondents who participated in the study. Data was collected using a questionnaire, an interview schedule and an observation schedule. The data collected was analyzed descriptively with the help of SPSS program version 17.0 for frequencies, means, standard deviation and percentages. The inferential statistics used to determine relationships among variables was the Pearson moment Correlation. Regression analysis was used to determine the best predictors of ICT integration among the independent variables. A p-value of less than 0.05 was interpreted as significant. Results indicated that there is a significant relationship between teacher-educators’ level of ICT integration in teaching and their age. However, the findings showed no relationships between teacher educators’ level of ICT integration in teaching and gender as well as their level of education. Teacher-educators’ years of teaching are insignificant in explaining teachereducators’ integration ICT in teaching. Based on the findings, we recommended that information and communication integration be made part of undergraduate training in universities in order to equip future teacher educators with ICT skills; planning for the implementation of ICT integration into teaching in teachers’ training programmes early would increase the pre-service teachers’ expertise and lead to an increase in the level of ICT integration during the earlier years of their careers. There is also need to hire young teacher-educators to the field, especially female teachers. This would also increase the representation of the female perspective toward the improvement of the level of ICT integration into teaching.
KerkoCite.ItemAlsoKnownAs: 2339240:3YGCEK6E 2339240:8DL2NNSV 2405685:M277EP4B 2405685:ZJ6CMABQ
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Lower Primary Levels Curriculum Designs, Volume 1: Kiswahili, Literacy and Indigenous Languages and English Activities - Kenya Institute of Curriculum Development (Kenya Institute of Curriculum Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:REAAQWHY 2405685:89EYMH85

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon; Mwanda, Samwel; Midigo, Ronnie; Maundu, John (American Journal of Education and Information Technologies, 2017)
The purpose of this study was to find out the extent of integration of computer technology into teaching and learning Biology in secondary schools of Rachuonyo South Sub-County, Kenya. The target population consisted of students and biology teachers in the Sub-County. Data was collected by use of questionnaires and an observation check list. From the study, most schools had few computers; teachers had inadequate training on use of computer applications; most teachers did not use computer technology for personal growth and instructional purposes. Inadequate number of computers in the sampled schools was the major challenge facing the integration of computer technology into the instruction process. The study recommends increased accessibility of computers, adequate training on use of computer technology and development of a policy framework to guide on the path to effective computer integration into instruction process.
KerkoCite.ItemAlsoKnownAs: 10.11648/j.ajeit.20170102.12 2339240:BB268PHG 2405685:N3QTNN5K
Keywords: ⚠️ Invalid DOI

Computer Laptop Project Strategy for Basic Education Schools in Kenya - Wambugu, Geoffrey M.; Ogenga, Stephen; Shikali, Casper; Muliaro, Joseph (2017)
Kenya’s Vision 2030 recognizes the enabling role of Information and Communication Technology (ICT) and anchors some of its key aspirations upon the availability and adoption of computers for schools. The overall objective of this strategy paper is to provide direction for acquisition of equitable and efficient laptop computers to all pupils in public primary schools. The existing education policy on ICT is imbedded in three documents namely; e-Government Strategy, National ICT Policy and Sessional Paper No. 1 of 2005 which is a Policy Framework for Education, Training and Research. There is a need therefore to consolidate these documents into one. The overall objective of the consolidation is to merge and integrate education policy on ICT including the scope, usage, administration and ways to address innovations and attendant Intellectual Property Rights. In the process of strategic planning for utilizing ICT in education, key stakeholders require to be consulted. In addition to the above mentioned, specific stakeholders include the National ICT integration and innovation Centre, Kenya Institute for Curriculum Development, Center for Mathematics, Science and Education in Africa, Teacher Service Commission, Primary Teacher Training Institutions, Universities and the National ICT Steering Committee. The strategy identifies the following as key weaknesses that hamper the implementation of ICT projects: slow integration of ICT in operations and programs; inadequate human and financial resources in some key service areas to meet the rapidly growing work-related demands. In addition there exists lack of appropriate learning facilities and/or infrastructure in some education and training institutions and inadequate number of trainers in modern technology coupled with a mismatch of skills learnt and demands of the labour market. It is also noted that the legal framework is non-harmonized and this inhibits the performance of Ministry of Education, Science and Technology. Further, a number of policy frameworks are yet to be operationalized thus hampering delivery of services. The strategy also identifies a Strategic Model for Laptop Project and an implementation matrix.
Accepted: 2017-09-08T06:46:45Z Publisher: IJICT Journals KerkoCite.ItemAlsoKnownAs: 2339240:2JE4BW6G 2339240:Q7M63VSV 2405685:RXLFLZGW 2405685:Z4L66S4G
Keywords: ⛔ No DOI found

Implementing mother tongue instruction in the real world: Results from a medium-scale randomized controlled trial in Kenya - Piper, Benjamin; Zuilkowski, Stephanie S.; Ong’ele, Salome (Comparative Education Review, 2016)
Research in sub-Saharan Africa investigating the effect of mother tongue (MT) literacy instruction at medium scale is limited. A randomized controlled trial of MT literacy instruction was implemented in 2013 and 2014 as part of the Primary Math and Reading (PRIMR) Initiative in Kenya. We compare the effect of two treatment groups—the base PRIMR program teaching literacy in English and Kiswahili and the PRIMR-MT program, which taught literacy in English, Kiswahili, and mother tongue—in two different language environments. Implementation of the MT program faced challenges because many educators were not speakers of the languages, some communities resisted mother tongue instruction, and some areas were more language heterogeneous. Effect sizes on MT literacy averaged between 0.3 and 0.6 standard deviations. The base PRIMR program also increased MT learning outcomes in some measures but had smaller effects than the PRIMR-MT program in oral reading fluency and comprehension.
Publisher: The University of Chicago Press KerkoCite.ItemAlsoKnownAs: 10.1086/688493 2405685:LXC5KVML 4042040:N6P4YDEN

Teachers' professional development in a challenging educational context – a study of actual practice in rural western Kenya - Onguko, Brown (University of Calgary, 2012)
This research adopted a design research approach, utilizing a mixture of methods including narratives, ethnographic observations, qualitative interviews and documentation of design artifacts. It was implemented in a challenging context in Western Kenya. The first research question for this study was: How might professional development (PD), offered through a blended learning approach and delivered by appropriate technologies, inform potential change to teaching practice in a challenging context in Kenya? Research question two sought to understand the implications of the professional development implemented in this study for teachers and professional development teachers (PDTs). Question three sought to understand the sustainability and scalability of the professional development approach The theoretical framework informing this research is based on activity theory- a needs-driven and goal directed process through tool mediation, and entails division of labor and isolation of partial tasks in a community of relationships (Vygotsky, 1978; Leont’ev, 1978; Engestrom, 1987; 1999; 2000; 2008). Key features of activity theory are active engagement and social interaction, which enabled teachers to collaboratively work with each other, studying through appropriate technologies to inform their teaching practices. Based on a review of literature, interviews with teachers and observation of teachers during face-to-face meetings in professional development and in their classroom practice, this study suggests that teachers in a challenging context can inform potential change to their teaching as a result of participation in locally developed content, delivered through blended learning on appropriate technologies. This study observes that through self-directed study on tablets, and occasional face-to-face interaction, teachers can transform into a community of learners that support each other in planning for their lessons. Content development involving local experts is critical to such interventions in challenging contexts, while drawing from global web content, harnessing open educational resources and being sensitive to local culture. Reflective conversations, professional dialogues and technology stewardship were all critical in informing teachers’ practice.
Publisher: Education KerkoCite.ItemAlsoKnownAs: 10.11575/PRISM/27984 2339240:DG2D5LEQ 2339240:HFGVU85N 2405685:3GUCVMD2 2405685:AJ9GX7EE 2534378:9XFBBTYJ 2534378:SQ7895I3
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2457443; __finaldtb; ⛔ No DOI found

Pro-Poor PRIMR: Improving Early Literacy Skills for Children from Low-Income Families in Kenya - Piper, Benjamin; Jepkemei, Evelyn; Kibukho, Kennedy (Africa Education Review, 2015)
Children from low-income families are at risk of learning outcome difficulties, particularly in literacy. Various studies link poor literacy results with performance later in primary and secondary school, and suggest that poverty, literacy skills and weak instructional methods combine to drastically limit the educational opportunities for many poor children. The Primary Math and Reading (PRIMR) Initiative was designed to support the learning gains of Class 1 and 2 pupils in seven counties across Kenya. PRIMR uses a randomised controlled trial design to establish the effect of its intervention and employs basic literacy measures to estimate causal effects. This study shows that PRIMR has been effective for children from low-income families and that early literacy interventions can mitigate socio-economic effects. The findings suggest that efforts to improve literacy outcomes for the poor should begin early in primary school. Strategies for ensuring that instruction is equitable across socio-economic status are advocated.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/18146627.2015.1036566 2339240:PG45F94W 2405685:772V2TVY
Keywords: Achievement Gains; Causal Models; Control Groups; Early Intervention; Early Reading; Educational Improvement; Effect Size; Emergent Literacy; Experimental Groups; Foreign Countries; Grade 1; Grade 2; Low Income Students; Oral Reading; Poverty; Randomized Controlled Trials; Reading Comprehension; Reading Fluency; Reading Tests; Regression (Statistics); School Effectiveness; Skill Development; Socioeconomic Status

Availability of Resource Materials and Facilities for ICT Integration in the Public Primary School Curriculum in Kitui County, Kenya - Mwendwa, Nzwili K. (2017)
Throughout the world, the Information and Communications Technology (ICT) is changing the face of education. This paper is a report of a study that was carried out in the months of May and June 2016 on the availability of resources and facilities for ICT integration in the public primary school curriculum in Kitui County in Kenya. The research purpose and objective of the study was: To find out the availability of resources and facilities for ICT integration in the public primary school curriculum in Kitui County. This study was guided by the Technology Acceptance Model (TAM). It was informed by the pragmatic philosophy and the Mixed Method (MM) research approach. Data was collected from 388 public primary schools in Kitui County selected through stratified and simple random sampling methods. A total of 388 head teachers and 776 teachers participated in the study giving a total of 1114 respondents. The research instruments used were questionnaires for teachers, interview schedules for head teachers and observation checklists. The data collected was analyzed qualitatively and quantitatively. The findings revealed that most of the schools were connected to electricity but lacked ICT resources such as desk computers, whiteboards, CD-ROMs and anti-viruses. Laptops were available in some of the schools but were not being used by teachers in direct instruction. They were mainly used in the storage of school records, teacher plans, examination questions and for examination registration exercises. Another finding was lack of internet connectivity in most of the schools that affected ICT integration in the curriculum. The study recommended that the education stakeholders and the government should partner in provision of ICT resources and facilities to facilitate integration of ICT in schools. It is hoped that this study will be useful in education policy making on ICT integration in schools in Kenya and other parts of the world.
Accepted: 2020-05-26T08:32:29Z Publisher: Scholars Middle East Publishers KerkoCite.ItemAlsoKnownAs: 2339240:UP3XU562 2405685:UDB54BE6
Keywords: ⛔ No DOI found

Role of ICT in Enabling High Quality OERs for Teacher Education and Training in Dadaab Refugee Settlement in Kenya - Ndalo, Agumba Musa (Research Journal of Education, 2016)
ICT and OER have the potential for uplifting the quality of refugee education across the world. Sustainable education in refugee camps/settlements is difficult to achieve in many countries that host refugees. This is because most international agencies that come to aid of the refugees are mostly concerned with basic humanitarian assistance like health, food and shelter. Quality education is a key determinant of students’ participation rates and achievement levels. It also remains an important ingredient towards attainment of social justice in terms of equity in educational quality for students. One contributing factor to quality education is availability of ICT infrastructure and quality OERs to create equity for many refugee learners in their camps. This paper describes how ICT and OER initiatives are appropriate tools for improving access, equity, and quality training and education of refugees in Dadaab refugee settlement schools in north eastern part of Kenya.
KerkoCite.ItemAlsoKnownAs: 2339240:9MAKBVX4 2405685:2ESBXBQX
Keywords: Google Scholar/ "refugee education" ICT; RER theme_supporting educators; ⛔ No DOI found

LEAP From Pilot to Scale: Embedding Digital Reading within the Kenya National Library Service - Heavner, Rachel; Lowe, Zev; Mwachi-Amolo, Joan (2017)
Mobile technologies have become more normalized for data collection, education for displaced communities and interventions at a distance. Yet, questions remain around how to effectively bring these technology interventions from pilot efforts to broad scale adoption. Worldreader is demonstrating operational success in its digital reading programs in Kenya. In 2014, Worldreader, in partnership with the Kenyan National Library Service (knls), launched its digital reading program, called LEAP (Libraries E-reading Activities Partnership) in eight libraries. By December 2017, LEAP had successfully scaled to all 61 public libraries in the country. This paper outlines five key insights for moving from pilot to country-level scale: 1. Start slow, start smart 2. Leverage economies of scale 3. Step by step: Implement in phases 4. Manage change: Creating a unified vision of success 5. Implement sustainability from the start. These learnings can inform others leveraging technology to improve education around the world and contribute to strengthening an effective, responsible and efficient ecosystem of technology-enriched educational programs.
KerkoCite.ItemAlsoKnownAs: 2339240:IGJL4PW2 2405685:GNGTW6N4
Keywords: ⛔ No DOI found

Does private schooling narrow wealth inequalities in learning outcomes? Evidence from East Africa - Alcott, Benjamin; Rose, Pauline (Oxford Review of Education, 2016)
In many low- and lower-middle-income countries, private schools are often considered to offer better quality of education than government schools. Yet, there is a lack of evidence to date on their role in reducing inequalities: namely, the extent to which private schooling improves learning among the most disadvantaged children. Our paper uses household survey data from Kenya, Tanzania, and Uganda to identify whether any observed impact of private schooling on core literacy and numeracy skills differs according to children’s household wealth. We demonstrate wealth gaps in access to private schooling, and use inferential models to account for observable differences between those who do and do not enrol in private schools. In Kenya and Uganda, we find that private schooling appears to improve the chances of children learning relative to their peers in government schools, but the chances of the poorest children learning in private schools remains low and is at best equivalent to the richest learning in government schools. In Tanzania, private schooling does not seem to improve poorer children’s learning, whereas it does for richer children. These findings raise a caution about the extent to which private provision can help narrow learning inequalities.
shortDOI: 10/gftss4 KerkoCite.ItemAlsoKnownAs: 10.1080/03054985.2016.1215611 10/gftss4 2405685:UIP8CZ6M 261495:Q3BWUMWN
Keywords: CitedIn:OER4Schools-HHH3-B; CitedIn:PhD_Thesis; East Africa; Kenya; Learning outcomes; Tanzania; Uganda; education policy; inequality; private schooling

Perspectives on underutilisation of ICT in education in Tanzania, Uganda and Kenya - Oroma, J. O.; Kiden, S.; Maghendha, M. W.; Ntiyani, S. (2013 IST-Africa Conference, 2013)
Developing countries in Africa have experienced considerably high growth in education that is witnessed by high enrolments at all levels, and brought forth several critical challenges like limited learning space, insufficient learning materials, and inadequate human capacity, forcing governments to build more schools and encourage the private sector to invest in education at all levels because education is pivotal to growth in other sectors. To overcome these challenges and improve the quality of education, these governments enacted several policies that integrate information and communication technologies in the curriculums at all levels of education and encouraged institutions to embrace these technologies because they enhance the teaching and learning processes. However, in reality, the adoption, ICT integration and implementation of these policies is inadequate and hindered by numerous factors. This study therefore focuses on exploring and comparing these factors leading to the underuse of ICT in education in these three countries.
KerkoCite.ItemAlsoKnownAs: 2339240:RWIB3G38 2405685:J9ABKGK8
Keywords: Africa; Computers; East Africa; Educational institutions; Government; ICT; ICT integration; ICT underutilisation; Internet; Kenya; Libraries; Materials; Tanzania; Uganda; Uganda and Kenya; challenges; computer aided instruction; context; countries; developing; developing countries; e-learning. Tanzania; education; education quality; educational institutions; excuses; human capacity; information and communication technologies; learning materials; learning process; learning space; private sector; teaching; teaching process; utilisation; ⛔ No DOI found

Internet Utilization: A Case of Connected Rural and Urban Secondary Schools in Kenya - Kiptalam, George Kibet; Rodrigues, Anthony Joachim (2013)
This paper looks at the utilization of the Internet among teachers and students in connected rural and urban secondary schools in Kenya. A conceptual framework composed of variables which can explain Internet utilization in Kenyan secondary schools is established and measured. Instruments based on this framework were used in the survey and covered 11 schools with school principals, teachers and students as respondents. Findings show that use of the Internet and its integration in teaching and learning in secondary education is increasing with its use more pervasive among students and teachers as a means of communication and for information searching. Internet access rates for teachers and students have been observed to be much higher in educational institutions that have made effective ICT investments in education, translating into better utilization of ICT related technologies. Strategies are suggested on how to utilize the Internet to improve educational outcomes, and recommendations given on issues that touch on ICT access and infrastructure; human resources and training; policy environment; financing and ICT investment; curriculum development and locally relevant content
KerkoCite.ItemAlsoKnownAs: 2339240:FCU9WCGE 2405685:2ZY6U5AA
Keywords: ⛔ No DOI found

An Evaluation of the Implementation of Information Technology in Secondary Schools in Kenya - Mbogo, Gracemary; Anne, Onunga; Kirathi, Miriam (Mediterranean Journal of Social Sciences, 2014)
Education is the best legacy a nation can give to her citizens especially the youth. This is because the development of any nation depends on the quality of education of such a nation. While ICT continues to advance in western Asia countries, African countries still experience a lag in its implementation and continues to widen the digital and knowledge divides. In a recent study by Kiptalam et .al (2010), observed that access to ICT facilities is against the ratio of 1:15 students in developed countries. This study was carried out to investigate the extent to which Information Technology has been implemented in secondary schools in Kenya. 30 teachers were sampled out from various counties. A questionnaire was administered to the sample. Descriptive statistics were used to analyze the data. The fidings indicated that most teachers appreciated the need to implement ICT in schools to enhance their effectiveness during the instructional processes. However, most of the teachers had limited ICT skills and rarely used ICT during their teaching. DOI: 10.5901/mjss.2014.v5n5p215
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2014.v5n5p215 10/gj37f2 2339240:4AHCXZ5X 2405685:7TLXRA2N

An Investigation into Implementation of ICT in Primary Schools, in Kenya, in the Light of Free Laptops at Primary One A Case Study of Teachers Implementing ICT into Their Teaching Practice - Tonui, Betty; Kerich, E; Koross, R (Journal of Education and Practice, 2016)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley region of Kenya. It examines views in pertinent literature as well as teachers’ perceptions of the benefits of integrating ICT into teaching-learning, the success factors and obstacles encountered in their endeavours to do this. Conclusions are drawn and suggestions made to address the challenges and improve on the use of ICT for teaching-learning in teaching institutions.
KerkoCite.ItemAlsoKnownAs: 2339240:RL8BR95I 2405685:SWCURERR
Keywords: ⛔ No DOI found

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (European Scientific Journal, ESJ, 2013)
Studies conducted in the field of ICT use in secondary schools reveal that, although in the past few years teachers and students have enjoyed adequate access to an assortment of ICTs such as computers, laptops, projectors printers, e-blackboards, mobile phones for use n integration of teaching and learning in schools, the level of utilization of the ICTs by teachers and students in Kitui District is still minimal. This study sought to examine the relationship between Principals, teachers’ and students’ attitude on utilization of ICTs and the readiness to adopt e-learning in curriculum implementation at secondary school level. The major objective of the study was to establish the extent to which the attitude of principals, teachers and students influence readiness to adopt e-learning in secondary schools in Kitui District. Cross–sectional survey research design was adopted for the study. A sample of 66 principals, 66 teachers and 347 students, were involved in the study. The multiphase sampling procedure was adopted for this study. Data were collected using questionnaires and an observation schedule. The resultant information was analyzed by employing the quantitative approach which involved descriptive and inferential statistical procedures. The findings of the study reveal that the attitude held by secondary school Principals and Teachers had no significant influence on the schools’ readiness to adopt e-learning. However, the attitude held by students had a significant influence on the schools’ readiness to adopt e-learning. The study recommends that the government should plan to address the issue of e-learning infrastructure by availing e-learning equipment, enhancing connection to reliable sources of power, improving connectivity to various internet services and augmenting Human Resource ﻿capacity by organizing training programmes for Principals, Teachers and Students. Secondary schools should employ support staff members such as computer laboratory technicians or assistants before embarking on full-scale implementation of e-learning in schools in Kitui District and, indeed, all other remote semi-arid districts in Kenya. This will enhance positive attitude and confidence that e-learning can be successfully adopted in secondary schools in Kenya regardless of the location of the school.
Number: 5 KerkoCite.ItemAlsoKnownAs: 10.19044/esj.2013.v9n5p%p 2339240:Y9XUMHZQ 2405685:7RWAJYSM
Keywords: ___working_potential_duplicate; ⚠️ Invalid DOI

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (European Scientific Journal, ESJ, 2013)
Studies conducted in the field of ICT use in secondary schools reveal that, although in the past few years teachers and students have enjoyed adequate access to an assortment of ICTs such as computers, laptops, projectors printers, e-blackboards, mobile phones for use n integration of teaching and learning in schools, the level of utilization of the ICTs by teachers and students in Kitui District is still minimal. This study sought to examine the relationship between Principals, teachers’ and students’ attitude on utilization of ICTs and the readiness to adopt e-learning in curriculum implementation at secondary school level. The major objective of the study was to establish the extent to which the attitude of principals, teachers and students influence readiness to adopt e-learning in secondary schools in Kitui District. Cross–sectional survey research design was adopted for the study. A sample of 66 principals, 66 teachers and 347 students, were involved in the study. The multiphase sampling procedure was adopted for this study. Data were collected using questionnaires and an observation schedule. The resultant information was analyzed by employing the quantitative approach which involved descriptive and inferential statistical procedures. The findings of the study reveal that the attitude held by secondary school Principals and Teachers had no significant influence on the schools’ readiness to adopt e-learning. However, the attitude held by students had a significant influence on the schools’ readiness to adopt e-learning. The study recommends that the government should plan to address the issue of e-learning infrastructure by availing e-learning equipment, enhancing connection to reliable sources of power, improving connectivity to various internet services and augmenting Human Resource ﻿capacity by organizing training programmes for Principals, Teachers and Students. Secondary schools should employ support staff members such as computer laboratory technicians or assistants before embarking on full-scale implementation of e-learning in schools in Kitui District and, indeed, all other remote semi-arid districts in Kenya. This will enhance positive attitude and confidence that e-learning can be successfully adopted in secondary schools in Kenya regardless of the location of the school.
Number: 5 KerkoCite.ItemAlsoKnownAs: 10.19044/esj.2013.v9n5p%p 2339240:Y9XUMHZQ 2405685:7RWAJYSM
Keywords: ___working_potential_duplicate; ⚠️ Invalid DOI

Teachers’ Perception About Integration of ICT in Teaching and Learning of Kiswahili Language in Secondary Schools in Kenya. - Miima, Florence; Ondigi, Dr Samson; Mavisi, Rose (2013)
This article discusses the results of exploratory study of integration of ICT in teaching and learning of Kiswahili language in Kenyan secondary schools taking the case of Kakamega county in western part of Kenya. A survey design technique was adopted. Forty five teachers were selected to act as sample size for the study. Questionnaires and interview protocols were used to collect the data. The data collected was analyzed through descriptive statistical techniques. The results are summarized and presented through tables and graphs. The findings established that most Kiswahili teachers understand the benefit of integrating ICT in teaching and learning of Kiswahili language but they are not willing to adopt it due to various challenges. The paper examines how Kiswahili language teachers integrate ICT into everyday classroom practice, their perceptions, constrains, and their reservations. It also considers use of ICT along with the influences of established curriculum practice and policy upon Kiswahili language teacher’s willingness to develop new forms of activity and pedagogy. The case study provides some information on integration of ICT at all level of language teaching and learning in education.
KerkoCite.ItemAlsoKnownAs: 2339240:877NW8X7 2405685:7X9VB3JM

Evaluation of the application of mobile phone technology in teaching and learning: A case study of Kamwenja Teacher' college, Nyeri County, Kenya. - Gitome, Mwangi Joseph (Mount Kenya University, 2015)
This research was designed to investigate the application of mobile phone technology in teaching and learning among tutors and students of Kamwenja Teachers College in Nyeri County in Kenya. The problem this study addressed was to establish whether mobile phones in the hands of students and tutors were beneficial for teaching and learning or if they impede learning process in Teacher Training Colleges in Kenya. The variables under consideration were: quality teaching and learning as dependent variable and owning mobile phones, awareness of educational potential of mobile phones, acceptance of mobile phones, and mobile phones influence as alternative learning and instructional methods as independent variables. The data was collected from 71 tutors and 498 students. The sample size was worked out at 20% to be 15 tutors and 100 second year teacher trainees in the college. Stratified random sampling was used to ensure the sample was a true representation of the whole population. Data was collected through questionnaires that were both quantitative and qualitative to ensure high quality of information for the study where 98.2% response rate was achieved. To ensure Validity and Reliability of Research Instruments a pre-test of the questionnaire was conducted on tutors and students of Kagumo Teachers College. A reliability coefficient of 0.7 was adopted for the items while an expert, the supervisor, guided in validity of the items. The study was guided by the activity theory also known as Cultural Historical Activity Theory. Primary data was analysed with the aid of Statistical Package for Social Sciences (SPSS version 20) software to generate descriptive statistics, correlation and multiple regression analysis. The findings of the study revealed that ownership of mobile phone had a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly and even when regressed together with other factors. Further, the study revealed that awareness of the educational potential of mobile phone technology, acceptance of mobile phone technology and mobile phone technology as an alternative learning and instructional methods were found to have a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly, however when all the factors were regressed together they were found to have a positive and but insignificant effect on application of mobile phone technology in teaching and learning. In order to enhance use of mobile phone technology in teaching and learning students and teachers should be encouraged to acquire mobile phones with internet connectivity features. The general usage of mobile phone in teachers training colleges was found to be very high. However the rate at which mobile phones are used for exchanging learning information is low. The researcher recommends that policies be put in place on use of mobile phone technology in teaching and learning and train tutors on how to teach differently using mobile phone technology. Future researchers should try to establish hindrances of application of mobile phone technology in teaching and learning.
Accepted: 2016-04-04T13:40:40Z KerkoCite.ItemAlsoKnownAs: 2339240:FXSLMRTK 2405685:6TXKF9WF

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, Eunice; Role, Jesse (2013)
The purpose of conducting this study was to determine the perception that students and teachers held on the utilisation of educational media in teaching and learning of History and Government subject in public secondary schools in Nandi Central Sub County, Kenya. The study involved participation of 10 secondary schools from the area. The target population for the study involved 48 teachers and 257 form IV students. The data for the research was collected through questionnaires. Research results showed that majority of student rated that educational media was very helpful in learning History and Government. Teachers had more positive perceptions towards the integration of educational media in teaching and learning of History and Government in secondary schools in Nandi Central Sub-County. There was a significant difference on the teachers perception and students perception on the use of educational media in teaching and learning History and Government in secondary schools (p<0.05). The study concluded that teachers and students perceived differently on the effect of utilisation of educational media in teaching and learning History and Government subject in secondary schools in Nandi Central. The study recommends that teachers should go for in-service training to be acquainted with new educational media resources. Teachers should also work closely with students when designing, improvising and utilising educational media resources in teaching and learning in schools.
KerkoCite.ItemAlsoKnownAs: 2339240:JXQX3HRX 2405685:A4NGYYZT
Keywords: ___working_potential_duplicate

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, E.; Role, Jesse (2016)
The purpose of conducting this study was to determine the perception that students and teachers held on the utilisation of educational media in teaching and learning of History and Government subject in public secondary schools in Nandi Central Sub County, Kenya. The study involved participation of 10 secondary schools from the area. The target population for the study involved 48 teachers and 257 form IV students. The data for the research was collected through questionnaires. Research results showed that majority of student rated that educational media was very helpful in learning History and Government. Teachers had more positive perceptions towards the integration of educational media in teaching and learning of History and Government in secondary schools in Nandi Central Sub-County. There was a significant difference on the teachers perception and students perception on the use of educational media in teaching and learning History and Government in secondary schools (p<0.05). The study concluded that teachers and students perceived differently on the effect of utilisation of educational media in teaching and learning History and Government subject in secondary schools in Nandi Central. The study recommends that teachers should go for in-service training to be acquainted with new educational media resources. Teachers should also work closely with students when designing, improvising and utilising educational media resources in teaching and learning in schools.
KerkoCite.ItemAlsoKnownAs: 2339240:PACAH3T8 2405685:LPWMW2HA
Keywords: ___working_potential_duplicate

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, Eunice; Role, Jesse (2013)
The purpose of conducting this study was to determine the perception that students and teachers held on the utilisation of educational media in teaching and learning of History and Government subject in public secondary schools in Nandi Central Sub County, Kenya. The study involved participation of 10 secondary schools from the area. The target population for the study involved 48 teachers and 257 form IV students. The data for the research was collected through questionnaires. Research results showed that majority of student rated that educational media was very helpful in learning History and Government. Teachers had more positive perceptions towards the integration of educational media in teaching and learning of History and Government in secondary schools in Nandi Central Sub-County. There was a significant difference on the teachers perception and students perception on the use of educational media in teaching and learning History and Government in secondary schools (p<0.05). The study concluded that teachers and students perceived differently on the effect of utilisation of educational media in teaching and learning History and Government subject in secondary schools in Nandi Central. The study recommends that teachers should go for in-service training to be acquainted with new educational media resources. Teachers should also work closely with students when designing, improvising and utilising educational media resources in teaching and learning in schools.
KerkoCite.ItemAlsoKnownAs: 2339240:JXQX3HRX 2405685:A4NGYYZT
Keywords: ___working_potential_duplicate; auto_merged

Impact of Information Communication Technology on Education-Kenya - Kirimi, Kagwiria Josephine (undefined, 2013)
Kenya has made remarkable progress putting in place an ICT policy framework and implementation strategy, complete with measurable outcomes and time frames. The process has had the benefit of sound advice from officials and stakeholders and, perhaps more importantly, strong leadership from the office of the permanent Secretary of the Ministry of Education. However, universal implementation is challenging given the lack of resources, national ICT infrastructure, and even electrical supply- particularly in the rural areas. As technology is bound to rule our present and future, it is good to obtain know-how of the technological reforms at the earliest. Children learn faster and can adapt to changes relatively easily. If they are trained during their school years, they have a high chance of becoming experts in technology. Computers can give lovelier explanations to various subjects. The internet is an ocean of information which can be harnessed for the rendition of information in school. The inclusion of technology in the learning process makes learning an enjoyable activity, thus inviting greater interest from the learners. The administration processes, the official procedures of the school can be simplified by the means of technology. School records, the information about all the students and the teachers and other school employees can efficiently be maintained by means of the advanced technology. Thus we see that technology not only benefits the school students but also eases the office work. It makes possible a more effective way of storage and distribution of information. The realization of the importance of technology in schools and its successful implementation is a necessity. The introduction of technology in schools is the means to bridge the long distance between the present and the future. DOI: 10.5901/jesr.2014.v4n1p435
KerkoCite.ItemAlsoKnownAs: 2339240:ARQM629G 2405685:IVSETB4P
Keywords: ⛔ No DOI found

Impact of Information Communication Technology on Education-Kenya - Kirimi, Josephine (Journal of Educational and Social Research, 2014)
Kenya has made remarkable progress putting in place an ICT policy framework and implementation strategy, complete with measurable outcomes and time frames. The process has had the benefit of sound advice from officials and stakeholders and, perhaps more importantly, strong leadership from the office of the permanent Secretary of the Ministry of Education. However, universal implementation is challenging given the lack of resources, national ICT infrastructure, and even electrical supply- particularly in the rural areas. As technology is bound to rule our present and future, it is good to obtain know-how of the technological reforms at the earliest. Children learn faster and can adapt to changes relatively easily. If they are trained during their school years, they have a high chance of becoming experts in technology. Computers can give lovelier explanations to various subjects. The internet is an ocean of information which can be harnessed for the rendition of information in school. The inclusion of technology in the learning process makes learning an enjoyable activity, thus inviting greater interest from the learners. The administration processes, the official procedures of the school can be simplified by the means of technology. School records, the information about all the students and the teachers and other school employees can efficiently be maintained by means of the advanced technology. Thus we see that technology not only benefits the school students but also eases the office work. It makes possible a more effective way of storage and distribution of information. The realization of the importance of technology in schools and its successful implementation is a necessity. The introduction of technology in schools is the means to bridge the long distance between the present and the future. DOI: 10.5901/jesr.2014.v4n1p435
KerkoCite.ItemAlsoKnownAs: 10.5901/jesr.2014.v4n1p435 10/gkm64d 2339240:SVPSUGP3 2405685:FYWRXAAR

Reward management strategies on employee performance in selected universities in Nakuru County, Kenya - Kathombe, Mary Wambui (Egerton University, 2018)
Rewards play an important role in increasing employee job satisfaction resulting in improving organizational performance. Motivated employees are the cornerstone of any successful organization. The main objective of this study was to establish the effects of reward management strategies on employee performance in selected universities in Nakuru County. The specific objectives were: to determine the effect of financial rewards on employee performance, to determine the effect of non-financial rewards on employee performance and to determine the combined effect of financial and non-financial rewards on employee performance. Descriptive survey design was adopted in conducting this study, as it was suitable for collecting information that described an existing phenomenon. The target population was 620 lecturers in two universities in Kenya namely Egerton and Kabarak Universities, which comprised a sample of 242 lecturers. The study primarily used a questionnaire to gather data from the respondents. Data from the questionnaire were systematically analyzed according to the research objectives and hypotheses. All hypotheses were tested using regression statistics and the results of the findings established that there is a strong positive association between combined effect of financial and non-financial rewards on employees‟ performance. According to the findings of this study, financial and non-financial rewards motivate employees to better performance. Thus, employee performance will be high in Kenyan universities that adopt an integrated effort on both financial and non-financial reward measurements. The study recommends the following: First, lecturers‟ promotion should be done regularly on merit. Secondly, Universities establish a competitive retirement benefit scheme to its employees. Third, Universities should engage their lecturers on regular training programs.
KerkoCite.ItemAlsoKnownAs: 2405685:VC2P9XQR

The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-year Account of Research in Kenya, Malawi and South Africa - Essien, Anthony (African Journal of Research in Mathematics, Science and Technology Education, 2018)
The purpose of this study was to provide a systematic review of research that has been carried out between 2006 and 2016 on the role of language in early grade (Grades 1–4) mathematics teaching and learning in three countries—Kenya, Malawi and South Africa. These countries were selected because they have similar characteristics: teaching and learning occur in a multilingual context; their language in education policies are similar; transition from mother tongue to English happens during the early grades; and most of the learners learn mathematics in English—a language which for most is not their first/home language. Research outputs between 2006 and 2016 from the three countries were sourced from peer-reviewed mathematics and general education journals, monitoring and evaluation reports, and book chapters. Findings from the study revealed that there is a lack of longitudinal studies that investigate the impact of language on the teaching and learning of mathematics and that there are few studies on how teachers are and should be trained to teach mathematics in the early grades. The study also found that the implementation of the language in education policies in the three different focus countries is fraught with difficulties owing to a number of factors, amongst them the fact that the indigenous languages are not yet fully developed as academic languages. Finally, existing literature highlights the importance of the use of code switching and the provision of materials in the home language(s) of early graders. Recommendations regarding policy/curriculum, teacher education and pedagogic practices are made.
KerkoCite.ItemAlsoKnownAs: 10.1080/18117295.2018.1434453 2405685:IWGA86UZ 4042040:U3N3KGSI

Challenges facing principals in Integrating Information Communication Technology (ICT) for efficient management in secondary schools In Nyamira County, Kenya - Ombui, Silas Chester (2013)
This study examines the challenges faced by Kenyan secondary school principals in the use of ICT in enhancing school management. The study investigated computer literacy levels of secondary school principals, challenges faced by principals in integrating ICT for management and acquiring computer hardware and software, extent in which ICT is being used in management and the recommendations which can enhance the principals use ICT for management. The target groups of schools under the study were schools situated in a rural district where we have weak infrastructure and limited facilities in terms of transportation and other means of communication. The study was conducted in 30 secondary schools in Nyamira District in Kenya selected purposefully using availability of electricity as the criteria for selection. Data collection methods included closed and open ended questionnaires for the principals and observation. The data collected was analyzed by tabulating the responses from the 30 respondents and processed manually using frequency counts and percentages. The study findings showed that ICT as a management tool was not used effectively to address management issues. The study also revealed that ICT was being used for clerical issues and to a limited extent on little management issues particularly the processing of examinations. The major challenges facing the principals was lack of funds to acquire computer hardware and software, lack of exposure on the capabilities of ICT to ease management work, and lack of adequate training in ICT for the principals. The findings of the study suggest that for successful implementation of ICT for management in Kenyan secondary schools, strategies that include the financing of ICT infrastructure by the government and other stakeholders, capacity building and the formulation of an ICT policy is required to address the issue of management in secondary schools. Equally adaptation of strategies used elsewhere in the world could be employed.
Accepted: 2013-09-09T06:59:21Z KerkoCite.ItemAlsoKnownAs: 2339240:WADVWVPF 2405685:HCBPD3VW 4656463:YKELQPB3

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Publisher: IISTE KerkoCite.ItemAlsoKnownAs: 2339240:VXMFTYG8 2405685:8FZZT8ZT
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

Strengthening Teacher Professional Development: Local and global communities of practice in Kakuma Refugee Camp - Mendenhall, Mary (Columbia University, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:7WPJ543M 2405685:32Z977JS
Keywords: C:Kenya / Rwanda

Preparedness of Public Secondary Schools on the Use of Information Communication Technology in Teaching and Learning in Mukurweini, Nyeri County-Kenya - Ngatia, Paul Kamau (Kenyatta University, 2015)
Globally the important role played by the use of Information and Communication Technology (ICT) in educational institutions has grown with states putting heavy investments in the purchase of ICT equipment and providing internet access for students and teachers. The Kenya government has been encouraging the adoption of ICT in schools. However, it is not clear to what extent this has been implemented. In Mukurwe-ini Sub County the implementation of ICT has not been effective as evidenced by Table 1.1. This study sought to assess the preparedness of public secondary schools on the Information Communication Technology (ICT) in Mukurwe-ini Sub County, Nyeri County. The study will assess the extent of use of ICT in secondary schools as well as investigate the school related and the teacher related preparedness to the use of ICT in their duties. The information obtained is helpful in assessing the implementation of government policy on ICT in schools. The study adopted descriptive survey design. The target population consisted; 31 public secondary school principals and 374 teachers in Mukurwe-ini Sub County. The researcher employed purposively, stratified random sampling techniques to select a sample of 15 schools, 15 principals and 120 teachers for the study. Data was collected using self-administered questionnaires. The questionnaires were assessed by experts in the field of educational technology to ensure validity while the reliability was tested using Cronbach’s alpha co-efficient calculated from the results of a pilot study and found to have a Cronbach’s Alpha Coefficient of 0.85. The study obtained both quantitative and qualitative data. Qualitative data were analysed thematically as per research objectives. Quantitative data were analysed by use of descriptive statistics in which measures of central tendencies such as mean, mode, and percentages were used for determination of extent of ICT, the level of school related and teacher related preparedness while inferential statistics specifically the independent sample t-test was used to test the relationship between variables using Statistical Package for Social Sciences (SPSS). It was found that teachers rarely used computers in teaching and learning. The school preparedness was poor with school environment and support being low while teachers had positive attitudes towards integration of ICT in teaching. However, teachers were found not to be well adequately trained and experienced in the use of ICT thus very low self confidence in use of ICT in teaching and learning. Conducive school environment that was supportive was found to have positive impact of integration of ICT, inadequate training and low self confidence hindered the adoption of ICT. The study recommended that the inclusion of ICT in curriculum in teacher training institutions, increased funding, provision up to date training of teachers and employment of technical support staff to improve ICT adoption in teaching and learning
Accepted: 2016-03-15T08:07:29Z KerkoCite.ItemAlsoKnownAs: 2339240:4XE4DQNW 2405685:CBCG2PVR

The Data Protection Act (No. 24 of 2019) - Republic of Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VXRC7SDS 2405685:K8JBSFIZ

Tusome and USAID Improve Access to Education - U.S. Embassy in Kenya (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:YB98PRXU 2405685:D9UIV9GZ

Guidelines on Parental Empowerment and Engagement - Kenya Institute of Curriculum Development (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:URALQWKL 2405685:VVJU6RCE

Pre Primary One Curriculum Designs - Kenya Institute of Curriculum Development (2017)
ISBN: 978-9966-31-712-4 KerkoCite.ItemAlsoKnownAs: 2339240:429B4H9H 2405685:SHXWMET5

Standards for Competence Based Digital Course Materials - Kenya Institute of Curriculum Development (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7JIAARG7 2405685:RUIF6MP8

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
EdTechHub.Copy: 2129771:3IIW96ZB shortDOI: 10/gftrqf KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 10/gftrqf 2129771:3IIW96ZB 2339240:AUEREUTT 2339240:NNWXI67C 2339240:QWI89XDJ 2339240:X37484JK 2405685:37II7RPP 2405685:4PBTS4CP 2405685:5LADY8ET 2405685:L36BGXMK 2405685:PT6BTPEC
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Basic education statistical booklet - Ministry of Education, Republic of Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:894SNAXV 2405685:49X4ADMZ

Assessment of public primary school teachers preparedness in the implementation of digital literacy programme in public primary schools in Imenti north sub-county, Kenya - Nyaga, Felistas (University of Nairobi, 2018)
The purpose of this study was to investigate the preparedness of public primary school teachers in the implementation of digital literacy programme in Imenti North Sub County Kenya. The study was guided by the following objectives; to establish infrastructural availability for the public primary school teachers’ usage in teaching and learning in implementation of digital literacy programme in public primary schools in Imenti North Sub County, to examine how public primary school teachers’ competence influence implementation of digital literacy program in public primary schools in Imenti North Sub County, The study sought to determine how public primary school teacher perception influence implementation of digital literacy program in public primary schools in Imenti North Sub County. The study also sought to establish how digital literacy content availability for the public primary school teachers influence implementation of digital literacy programme in public primary schools in Imenti North Sub County. The study adopted descriptive research design. The study was grounded on technology diffusion theory to explain the relationship between the independent and dependent variables. The study had a target population of 596 respondents who comprised 59 head teachers and 537 teachers. The respondents were selected using proportionate random sampling technique where by a sample size of 137 was used. Primary data was obtained using self-administered questionnaires that were made up of both open ended and closed ended questions, also unstructured interview was administered face-to-face or over the phone. The reliability of the study was measured using test retest method. The Data was analyzed using Statistical Package for Social Sciences and the data was presented in frequency tables, percentages and regression analysis. The study concluded that preparedness of public primary school teachers in the implementation of digital literacy programme was highly influenced by teacher competence followed by infrastructural preparedness and then by Teacher perception while digital literacy content had the least effect on implementation of digital literacy programme in public primary schools in Imenti North Sub County. The study concluded that infrastructural preparedness influences implementation of digital literacy program in public primary schools in Imenti North Sub County significantly. Even though the schools have electricity their computer lab have not been fully equipped. The implementation of digital literacy program has been delayed by inadequate internet connections coupled with inadequate digital literacy program devices for teaching and learning in the schools. Also, there being inadequate tablets for the learners and laptops for the teachers have negatively affected the implementation of digital literacy program in public primary schools. The study recommends that teachers and instructors need to be trained in basic ICT skills and ICT-based teaching methods to feel comfortable about using the materials. The study recommends that the governments should ensure that all the public primary schools are connected to wireless internet services; that primary schools should be assisted by both national and county government need to ensure that the schools have a complete computer lab that is fully equipped with enough laptops for the teachers and tablets for the learners. The study further recommends that head teachers and parents need to set up administrative committees to manage ICT facilities as proven to be very effective in ensuring the sustainability of initiatives.
Accepted: 2018-10-18T13:52:29Z KerkoCite.ItemAlsoKnownAs: 2339240:3QH6L8SL 2405685:C6Y4LLKR

"For us it was a learning experience": design, development and implementation of blended learning - Onguko, Brown; Jepchumba, Lucy; Gaceri, Petronilla (European Journal of Training and Development, 2013)
Purpose - The purpose of this paper is to share reflections of the three authors on the process of instructional design and implementation of blended learning for teachers' professional development (PD) in rural western Kenya. It proposes reforms in provision of teachers' professional development to enable professional development providers to access specialized skills in instructional design (ID) and blended learning. Design/methodology/approach - The paper resulted from a design-based research including 12 entry and 12 exit interviews, observations of three face-to-face meetings of blended learning sessions and ten classroom observations of teachers implementing new teaching approaches learned through blended learning. Findings - The paper provides insights into the authors' experiences in this research. They shared the following reflections: engagement in ID empowered them and they are confident that they can engage in systematic instructional design on a larger scale; they gained technical knowledge and skills in authoring content in HTML on eXe open source platform; uploading the content and processing audio and video content was equally enthralling to them. Research limitations/implications - Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to consider incorporating the design-based research, instructional design and blended learning approaches used in this study while conducting related research in their dissimilar contexts. Practical implications - The paper includes implications for the design, development and implementation of teachers' professional development for challenging contexts as a contribution towards achievement of both Millennium Development Goals (MDGs) and Education for All (EFA). Originality/value - This paper fulfils an identified need to study provision of professional development for teachers who lack opportunities for professional development.
Place: Limerick Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1430572667?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/ejtd-10-2012-0052 2339240:C7CEXRWM 2339240:XN53EQR3 2405685:AFTT7Q76 2405685:UYED6EDY 2405685:ZZ7VUU4G 2534378:32ICX4DB 2534378:UTXP2X7Q
Keywords: 5220:Information technology management; 8306:Schools and educational services; 9177:Africa; Appropriate technology; Audio recordings; Business And Economics–Management; Instructional design; Kenya; Personal development; Professional development; Research; Rural schools; Teaching; Technological change; Training; __:import:01; __:match:final; __:matched; __:study_id:2096396; ___working_potential_duplicate; __finaldtb

School governance, teacher incentives, and pupil–teacher ratios: Experimental evidence from Kenyan primary schools - Duflo, Esther; Dupas, Pascaline; Kremer, Michael (Journal of Public Economics, 2015)
Some education policymakers focus on bringing down pupil–teacher ratios. Others argue that resources will have limited impact without systematic reforms to education governance, teacher incentives, and pedagogy. We examine a program under which school committees at randomly selected Kenyan schools were funded to hire an additional teacher on an annual contract renewable conditional on performance, outside normal Ministry of Education civil-service channels, at one-quarter normal compensation levels. For students randomly assigned to stay with existing classes, test scores did not increase signiﬁcantly, despite a reduction in class size from 82 to 44 on average. In contrast, scores increased for students assigned to be taught by locally-hired contract teachers. One reason may be that contract teachers had low absence rates, while centrally-hired civil-service teachers in schools randomly assigned contract teachers endogenously reduced their effort. Civil-service teachers also captured rents for their families, with approximately 1/3 of contract teacher positions going to relatives of existing teachers. A governance program that empowered parents within school committees reduced both forms of capture. The best contract teachers obtained civil service jobs over time, and we estimate large potential dynamic beneﬁts from supplementing a civil service system with locally-hired contract teachers brought in on a probationary basis and granted tenure conditional on performance.
shortDOI: 10/f68tj3 KerkoCite.ItemAlsoKnownAs: 10.1016/j.jpubeco.2014.11.008 10/f68tj3 2405685:MC4383YQ

Third Medium Term Plan 2018-2022 - The National Treasury and Planning (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:FG8UXQP8

Ministry of Information, Communications and Technology, Innovation and Youth Affairs (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:WL8CUUV2

The Centre for Innovative Teaching and Learning Approach - Mastercard Foundation (2019)
Library Catalog: mastercardfdn.org KerkoCite.ItemAlsoKnownAs: 2405685:VLG3BPAQ

EdTech East Africa (Edtech Meetup, 2017)
Library Catalog: edtecheastafrica.com EdTechHub.ItemAlsoKnownAs: 2405685:GN64Y5CP

Research methods dictionary - Mugenda, Olive M; Mugenda, Abel G (Kenya Arts Press, 2012)
KerkoCite.ItemAlsoKnownAs: 2405685:HQRL48EG

Case Study Report: RET International Kenya - Boisvert, Kayla (University of Massachusetts Amherst, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZPJGD9MB 2405685:SACV4G7Q

Implementing large scale instructional technology in Kenya | RTI - Piper, Ben; Oyanga, A; Meija, J; Pouezevara, S (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:EDUQCBQZ 2405685:6JAG9EUA

Impact evaluation of Tayari school readiness program in Kenya - Ngware, Moses; Hungi, Njora; Wekulo, Patricia; Mutisya, Maurice; Njagi, Joan; Muhia, Nelson; Wambiya, Elvis; Donfouet, Hermann; Gathoni, Grace; Mambe, Shem (APHRC, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:547KU8IY 2405685:ZPLJMSX2

Boosting Prosperity, Improving Equity in North and North Eastern Kenya - World Bank (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:9V2IVCR2 2405685:4Y9H2JHW

Accessibility and Utilization of ICTs Among Secondary School Teachers in Kenya - Kiptalam, GK; Rodrigues, AJ (2010)
KerkoCite.ItemAlsoKnownAs: 2339240:3EPLC3Q9 2405685:LRH5W4WW
Keywords: ⛔ No DOI found

Teachers’ attitudes towards the utility of computers in education in Kenya - Buliva, Newton (African Educational Research Journal, 2018)
KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.61.18.004 10.30918/aerj.61.18.004 10/gj37d7 2339240:7GZZFLDB 2405685:UDGTWCSZ

In Bringing a Literacy Project to Scale, has Kenya Found a Holy Grail? - Bruns, Barbara (Center For Global Development, 2018)
An article of faith among development economists is that “evidence-based policy” holds the promise of faster progress. Barbara Bruns set out to find a rigorously evaluated pilot whose evidence had led to a program at scale. It wasn’t easy.
KerkoCite.ItemAlsoKnownAs: 2129771:2D7IEEZ6 2339240:GIKWZG8S 2405685:IUEBJUAM

Mobile Data Plans in Kenya. Quantifying Women's Access to the Digital World - Gemeda, B.T.; Thakur, D. (Alliance for Affordable Internet, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:HRY4VJMC 2405685:KMJJPPRF

246 6 Accessibility and Utilization of ICTs Among Secondary School Teachers in Kenya - University, G. (2010)
This paper looks at levels of access and extent of use of Information and Communication Technologies (ICTs) among teachers in selected Kenyan secondary schools. For the past few years, an assortment of ICTs such as computers, lap tops, projectors, printers, e-blackboards and mobile phones have been available to teachers for use in integration of teaching and learning in schools. The paper attempts to establish how many teachers have access to the schools’ computers, their ICT literacy skills level and the level of ICT integration in subjects taught. The findings show that the use of ICT and its integration in the teaching and learning in secondary education is getting more widespread; and increasingly used among teachers as a means of communication and for information searching. Access rates for teachers have been observed to be much higher in educational institutions that have made effective ICT investments in education, translating into better utilization of ICT related technologies. Strategies have been suggested on how to utilize ICT to improve educational outcomes and recommendations given, on issues that touch on ICT access and infrastructure; human resources and training, policy environment, financing and ICT investment, curriculum development and locally relevant content.
KerkoCite.ItemAlsoKnownAs: 2339240:FR7DD5E8 2405685:8Z2L4L66

Parental Involvement in Primary Schools in Kenya as a Major Strategy for Academic Success - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
KerkoCite.ItemAlsoKnownAs: 10.46827/ejes.v0i0.2011 2339240:DIGA96IK 2405685:YUHYVPSU
Keywords: ⚠️ Invalid DOI

Mathematics from the beginning: Evaluating the Tayari preprimary program’s impact on early mathematics skills - Piper, Benjamin; Sitabkhan, Yasmin; Nderu, Evangeline (Global Education Review, 2018)
Given the dearth of research on early numeracy interventions in low- and middle-income countries, this paper presents the instructional methodology and impact results of the Tayari program. Tayari is a preprimary intervention in Kenya (2014–2019) that prepares children aged four and five for entry into primary school through materials for students, training for teachers, and continuous in-classroom support. Evidence points to the long-term benefits of developing an early foundation in mathematics. The few preprimary mathematics studies in sub-Saharan Africa have not described the instructional methodology in enough detail to add to our knowledge of best practices. The Tayari methodology was built on the Kenyan government’s preprimary syllabus to produce instruction that was developmentally sequenced, linked to out-of-school experiences, and supportive of children’s number sense. Tayari is evaluated using a randomized controlled trial (RCT) and collection of longitudinal data from 2,957 children in treatment and control schools at three time points. Pupil assessment items were drawn from a growing body of research on preprimary numeracy in developing contexts, plus instruments and techniques from the Measuring Early Learning and Quality Outcomes (MELQO) program (UNESCO, UNICEF, Brookings Institution, & World Bank Group, 2017). The endline impact evaluation of the longitudinal RCT results showed statistically significant effects in the numeracy tasks of producing sets, identifying numbers, and naming shapes, while revealing no initial effects in the areas of oral and mental addition. We present recommendations for Tayari’s improvement in terms of mathematics instruction, as well as preprimary policy implications for Kenya and similar contexts.
Number: 3 KerkoCite.ItemAlsoKnownAs: 2339240:NZYMKPRM 2405685:FE8S3EHI
Keywords: Sub-Saharan Africa; ⛔ No DOI found

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon (International Journal of Education, Culture and Society, 2017)
KerkoCite.ItemAlsoKnownAs: 10.11648/j.ijecs.20170206.12 10/gj37fw 2339240:U7RM2HPH 2405685:UUD5WNGX

Opportunities and Challenges: Integration of ICT in Teaching and Learning Mathematics in Secondary Schools, Nairobi, Kenya - Amuko, Sheila; Miheso, Marguerite; Ndeuthi, Sophie (Journal of Education and Practice, 2015)
This presentation is based on a larger study whose purpose was to explore the various opportunities and challenges influencing integration of ICT in teaching and learning Mathematics in secondary schools in Nairobi County. The study, adopted a descriptive survey design. Three instruments questionnaires’, a structured interview schedule and an observation checklist were used to collect data. The study was carried out in twelve public secondary schools in Nairobi County. Data was analysed using descriptive statistics. Findings from the study indicated that, teachers face major challenges such as developing their own technological skills and knowledge as well as self-training in the use ICTs in their teaching. This lack of capacity building support was found by the study to contribute to teacher lax in integrating technology in their teaching inspite of the enthusiasm. This study recommends that new frontiers on technology integration be made accessible to both teachers and students for learning purpose to increase access to information and that, capacity building in technology integration be increased for teachers and awareness be built among pre-service teachers trainees integrating ICT in teaching and learning Mathematics.
KerkoCite.ItemAlsoKnownAs: 2339240:7W48235D 2339240:8DMEMD5P 2339240:SIDJRTGQ 2405685:VGHI2VJJ 2405685:WP5KHL7M 2405685:XBZN4W7Q
Keywords: Barriers; Check Lists; Foreign Countries; Knowledge Level; Mathematics Instruction; Observation; Public Schools; Questionnaires; Secondary School Mathematics; Secondary School Teachers; Statistical Analysis; Structured Interviews; Surveys; Teacher Attitudes; Teacher Competencies; Teacher Education; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; ___working_potential_duplicate; ⛔ No DOI found

Teachers’ Perception About Integration of ICT Tools in Kiswahili Language Pedagogy in Homabay County, Kenya - Ochieng, BENSON ONYANGO; Miima, FLORENCE ABUYEKA (International Journal of Arts and Commerce, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:E552R7C3 2405685:IEG3IU97

Promoting gender equality in education in Kenya: A case for innovative programmes to bridge the divide - Kinyanjui, Joyce (Buwa, 2016)
This issue of BUWA explores these questions and provides space for African women and men to define the kind of education that can meet SDG goals. Articles in the issue assess the existing policy frameworks and the officially stated drivers which are shaping them as well as those which are not stated. The various tested and emerging untested models for delivering quality education for women and girls on the continent are considered, as well as key questions around innovative, robust financing models and challenges for education. The main focus here is the extent to which the provision of quality education has to be fully catered to through domestic finances and resources – both for sustainability and ownership purposes.
KerkoCite.ItemAlsoKnownAs: 2339240:PIIQUFZE 2405685:KSA23BE4
Keywords: Equity through Access; ⛔ No DOI found; ⛔ No INSPIRE recid found

The effect of free primary education policy on late school entry in urban primary schools in Kenya - Ngware, Moses W.; Oketch, Moses; Ezeh, Alex C.; Mutisya, Maurice (International Review of Education, 2013)
KerkoCite.ItemAlsoKnownAs: 10.1007/s11159-013-9389-6 2405685:JH6YHV6A

Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics: - Kiboss, Joel Kipkemboi (Journal of Educational Computing Research, 2012)
Achievement in mathematics is an issue of great concern not only to students and parents but also to employers and researchers in Kenya. This is because the Ken...
Sage CA: Los Angeles, CA shortDOI: 10/ggdtp3 KerkoCite.ItemAlsoKnownAs: 10.2190/EC.46.1.b 10.2190/ec.46.1.b 10/ggdtp3 2339240:E2A49LQS 2339240:SRIBPMIE 2405685:TBHFERAU 2405685:Z3BJFVR2

Anasoma Mid-Term Report - Worldreader; R4D (Worldreader, 2017)
This report shows the initial findings of the first sprint of the Anasoma Research aimed at identifying barriers of and drivers to female mobile readership in Kenya.
KerkoCite.ItemAlsoKnownAs: 2339240:9NYR4VUI 2405685:ZQ33H7RV

Tusome Early Grade Reading Activity - RTI International (RTI, 2016)
Across Kenya, literacy rates in primary schools are significantly lower than expected despite increased access and enrollment. The Kenyan education system is seeking to improve learning outcomes by instilling better instructional practices, expanding resources for teacher training, and developing learning materials that support multilingual literacy. Kenya’s approach to the challenge of raising literacy and learning outcomes is unique in its ambitious goals and well-researched methods for achieving its goal at a national scale.
Library Catalog: www.rti.org EdTechHub.ItemAlsoKnownAs: 2405685:TQJGJK6H

Influence Of Hidden Costs In Education On Students’ Participation In Public Secondary Schools In Kikuyu Sub County, Kenya - Kingori, Joseph Ndirangu (School of Education Department of Educational Administration and Planning of Nairobi University, 2015)
KerkoCite.ItemAlsoKnownAs: 2405685:VJRWLGGE
Keywords: ⛔ No DOI found

Kids hacker camps in Kenya | Proceedings of the Seventh International Conference on Information and Communication Technologies and Development - Ndaiga, Wachira; Salim, Anne (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:L64R4AUI 2405685:CZD5X8NE

ICT in secondary school administration in rural southern Kenya: An educator’s eye on its importance and use - Makewa, Lazarus; Meremo, Jackson; Role, Elizabeth; Role, Jesse (2013)
This study investigated whether there was a significant difference between teachers’ and administrators’ perceptions on the importance of Information and Communications Technologies (ICT) in secondary school administration and evaluated the extent to which it was used by administrators. In this study, administrators are those involved in the day to day running of secondary school duties such as: the principal, deputy principal and heads of departments. The researchers used a descriptive-comparative research design to obtain information on the current status of ICT. The t-test was used to establish whether there was any significant difference in perceptions while a Pearson product-moment correlation coefficient was used to find whether there was any significant relationship between educators’ perceptions of the importance and extent of ICT use in secondary school administration. Both teachers and administrators rated the use of ICT in secondary school administration as important. Teachers and administrators viewed the use of ICT in student administration as equally important. Administrators rated the importance of using ICT in supervision of instruction and in student administration more highly. There was a significant difference between the perceptions of teachers and administrators on the importance of ICT use in the following areas of secondary school administration: student administration, general administration and supervision of instruction.
KerkoCite.ItemAlsoKnownAs: 2339240:8CTPMNKU 2405685:W5EYUSLQ
Keywords: ⛔ No DOI found

Influence Of Hidden Costs In Education On Students’ Participation In Public Secondary Schools In Kikuyu Sub County, Kenya - Kingori, Joseph Ndirangu (School of Education Department of Educational Administration and Planning of Nairobi University, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:233GFMV3 2405685:QR4WZLL3

Impact of non-financial reward strategies on teachers’ performance: A study of secondary schools in Nyamira County, Kenya - Mochengo, Sylvester Nyageo; Atambo, Wallace; Abuga, Mogwambo Vitalis (European Journal of Business and Management, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:NK4YZG8L
Keywords: ⛔ No DOI found

Enhancement of Science Performance through Computer Assisted Instruction among Selected Secondary School Learners in Kenya | Dr. Samuel N Jesse - Academia.edu - Jesse, Samuel (2014)
KerkoCite.ItemAlsoKnownAs: 2339240:PZPJ3Y73 2405685:SFD4AHGW

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Publisher: Horizon Research Publishing KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 10/gf622k 2339240:FWBVWVA2 2405685:ARBG7E6A
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Dr Angeline Sabina; Kyalo, Dr Dorothy Ndunge (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:5BBVKX84 2405685:SGP9493Q
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Design and development of a Web Based Learning System in lower primary schools: A Case study of Makini Primary School, Kenya - Akinyi, Beatrice Ochieng (Moi University, 2015)
Web design technology arises from continued technological trend of computing. Globally the rise of application of information communication technology to the learning programme of primary schools is not much emphasized on. There is empirical evidence to prove that information communication technology is highly beneficial wherever it is applied. The study aimed at designing and developing a web based system of learning that can enhance the academic and social growth of lower primary school pupils. The objectives of the study were: to examine the correlation between the increased use of web based systems of learning and learner‟s academic performance; to identify the set of skills required for lower primary pupils to fully exploit the potential of web based systems of learning; to find out the specification and technical attributes of web based systems of learning that facilitate learning and lastly to design a web based learning system for lower primary school pupils. The study focused on Makini lower primary school in Nairobi County. The study employed case study method and qualitative approach. Rapid Application Development life cycle was used in software development process. Purposive sampling method was used to identify the respondents. Data was collected using interviews and focus group discussions. Findings of the study were: increased use of web based system that enhanced the learner‟s academic performance, the web based system of learning was able to identify games which exploit the pupils‟ skill in learning hence reducing monotony and lastly the web based system was able to identify some technical attributes such as use of graphics and access rights that facilitated learning and testing. The conclusion showed that developing of a web based learning system would reduce monotony in learning and enabled pupils to be in control and also increased the creativity and thinking level. The study recommends that: additions be made to the system such as a module to generate a feasible master timetable for each teacher; the web application of the system be further expanded to help attendance recording by the class teacher and for the parents to be able to view the status of their children performance using the Internet or Intranet of the school and lastly the system be made for every teacher to have some specific free periods or some part of days off and that will require an efficient search technique.
Accepted: 2018-07-19T06:28:17Z KerkoCite.ItemAlsoKnownAs: 2339240:2NYT4UPN 2339240:9UIGBGDA 2405685:II4IEI4L 2405685:UZS2AQCD
Keywords: ___working_potential_duplicate

Use of Information communication technology in teaching and learning processes in secondary schools in Rachuonyo South District, Homa-Bay County, Kenya - Obonyo, Samson O. (University of Nairobi, 2013)
The purpose of this study was to investigate the use of Information Communication Technology (ICT) in teaching and Learning in Rachuonyo South District secondary schools. The focus was on three main subject matters: on ICT use and competence, on teacher and student and on ICT infrastructure and teaching practices. The study is closely connected to the national educational policy, which has aimed strongly at supporting the implementation of ICT in pedagogical practices at all institutional levels. Six research questions were formulated to guide the researcher investigate the phenomena. A descriptive survey design was used to collect data from the field through the use of questionnaire and an observation schedule. The result indicated that ICT has not been successfully integrated in teaching and learning in schools. In general, students are capable and motivated users of computers. Some students have the skills to use new kinds of applications and their ICT skills are wider although not necessarily adequate. Teachers’ skills are more heterogeneous. The large majority of teachers have sufficient skills for everyday and routine working practices, but many of them still have difficulties in finding a meaningful integration of ICT into teaching and learning. Most teachers reported that the use of ICT in learning and teaching was slow in the past years and proposed upgrading of students computer labs and accelerating internet connectivity in the schools. Further, teachers’ good ICT competence helps them to adopt new pedagogical practices and integrate ICT in a meaningful way. The results also showed that students are capable and motivated users of new technology and their ICT skills are wide, although not necessarily adequate; the working habit might be ineffective and wrong. Some students have a special kind of ICT related adaptive expertise, which develops in a beneficial interaction between students and teachers, and individual interest and activity. The most common goal to student use of ICT is challenged by the internet, digital communication and the need to filter information. Since students’ ICT skills can be translated to increased creativity, which include innovation and productive workforce, to develop capacity to ICT which support the country’s knowledge base. The findings further indicated that ICT integration realized some challenges such as availability of sufficient number of ICT tools, lack of motivation and support and lack of technical support. The challenges are either teacher-level (Microlevel), school level (Meso-level) or system level (Macro-level). These barriers have hindered successful implementation of ICT into teaching and learning processes. The study also recommended that teachers should be given sufficient training on how to use ICT tools to enhance teaching and learning in schools. The study also recommended that students should be equipped with ICT skills such as Microsoft software applications such as word, excel and access. Finally, further research on the perception of teachers and students towards the use of ICT in enhancing teaching and learning and relevant strategies for using ICT to improve teaching and learning practices should be conducted.
Accepted: 2013-09-13T12:53:42Z KerkoCite.ItemAlsoKnownAs: 2339240:VMGJH5RH 2405685:K3FR5Q2D

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Dr Angeline Sabina; Kyalo, Dr Dorothy Ndunge (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:5BBVKX84 2405685:SGP9493Q
Keywords: ___working_potential_duplicate; ⛔ No DOI found

‘Now I want to use it to learn more’: Using mobile phones to further the educational rights of the girl child in Kenya - Zelezny-Green, Ronda (Gender & Development, 2018)
Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 10.1080/13552074.2018.1473226 2339240:83S7BWWP 2405685:JTAQVM9P
Keywords: Equity through Access; ⛔ No INSPIRE recid found

Teachers as Guides: The role of teachers in the facilitation of technology-mediated learning in an alternative education setting in western Kenya - Radhakrishnan, Dhinesh; DeBoer, Jennifer; Kimani, Samuel (Purdue University, 2018)
KerkoCite.ItemAlsoKnownAs: 10.5703/1288284316852 2339240:6MVFIILP 2405685:9HDGMXSH

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, Eunice; Jesse, Role (International Journal of Science and Research (IJSR), 2016)
Call for Papers - International Journal of Science and Research (IJSR) is a Fully Refereed - Peer Reviewed International Journal. Notably, it is a Referred, Highly Indexed, Online International Journal with High Impact Factor.
Publisher: International Journal of Science and Research (IJSR) KerkoCite.ItemAlsoKnownAs: 2339240:VSUACQ2E 2405685:HCBCP5Q7
Keywords: ___working_potential_duplicate; ⛔ No DOI found

JiFUNzeni: a blended learning approach for sustainable teachers' professional development - Onguko, Brown Bully (Electronic Journal of e-Learning, 2014)
JiFUNzeni blended learning approach is a sustainable approach to provision of professional development (PD) for those in challenging educational contexts. JiFUNzeni approach emphasizes training regional experts to create blended learning content, working with appropriate technology while building content repositories. JiFUNzeni approach was fieldtested though a design-based research intervention conducted in rural western Kenya. The field test included design, development and implementation of a blended learning course for teachers’ professional development utilizing appropriate technologies including tablets powered by solar energy, open educational resources and open source software. One year after the intervention, follow-up interviews were conducted with eight of the ten teachers and two professional development tutors (PDTs) who participated in the research. The findings from the follow-up interviews shared in this paper revealed that: teachers still used cooperative learning and activity-based learning strategies in their teaching. The PDTs on the other hand designed, developed and implemented one other jiFUNzeni blended learning course for twelve teachers in one school in Korogocho slum in Nairobi city. Implementation by PDTs of jiFUNzeni approach confirmed that they had learned through a sustainable way of delivering professional development in challenging educational contexts. The PDTs utilized the instructional design approaches learned through their participation in the research in designing blended learning content, while they also innovated new ways of developing self-study content as an important creative addition to what they had previously learned. Two teenage children participated in digital content development by advising the PDTs on some appropriate ways of applying technology thus, attesting to the fact that digital natives are important reciprocal supporters to digital immigrants and vice versa.
KerkoCite.ItemAlsoKnownAs: 2339240:5SCGRA3U 2339240:M7R5EIZL 2339240:TS6R3E24 2339240:VWE52LMG 2339240:YMBURAH4 2405685:AKXHE6HE 2405685:Q3Y6Z65Z 2405685:U5WZEBXT 2405685:UNATTHSB 2405685:XVE57FFE 2534378:7WCVV8XM 2534378:DW5I8PW4 2534378:T6RRJMGR
Keywords: Blended Learning; Computer Software; Computers; Cooperative Learning; Cooperative learning; Course Content; Design; Disadvantaged Environment; Distance learning; Education–Computer Applications; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Internet; Interviews; Kenya; Learning Activities; Multimedia Materials; Open Source Technology; Program Development; Qualitative Research; Rural Areas; Self Evaluation (Individuals); Sustainability; Teacher Attitudes; Teaching Methods; Training; __:import:01; __:match:final; __:matched; __:study_id:2096405; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

UIS Statistics - UNESCO Institute for Statistics (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:D63GEHHY 2405685:IZ8998MR 2405685:WTPRBCKB
Keywords: ___working_potential_duplicate

UIS Statistics - UNESCO Institute for Statistics (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:D63GEHHY 2405685:IZ8998MR 2405685:WTPRBCKB
Keywords: ___working_potential_duplicate

Use of low cost wireless communication technology for education in rural Kenya | Proceedings of the 4th ACM Workshop on Networked Systems for Developing Regions - Mayeku, B.; Kilwake, J.; Bertarelli, F (2010)
KerkoCite.ItemAlsoKnownAs: 2339240:MM4XR5EJ 2405685:8D3XN52L

Innovation: Instant Network Schools open up a new world for Somali refugees - Ostermann, Silja (United Nations High Commissioner for Refugees, 2015)
DADAAB, Kenya, February 4 (UNHCR) - Thirty pairs of fascinated eyes watch the big white screen; fingers glide across new tablet computers. A class of students at the Nasib Secondary School in north-east Kenya's Dadaab refugee camp complex, is enjoying a history lesson about the Portuguese in Africa. Most have spent their whole life in the arid camps of Dadaab. They have never even visited the closest Kenyan city, Garissa, which is located two hours away by road. But today they are travelling through Africa and the past - online.
KerkoCite.ItemAlsoKnownAs: 2339240:5DP3HMRA 2405685:9KQMBUJW 6018420:AUU5ZCC2

Project Appraisal document on a Global Partnership for Education Fund grant in the amount of US$88.4 million to the Republic of Kenya for a primary education development project - World Bank (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:P64JSJCL 2405685:P2NM7XXB

Four cautionary lessons about education technology - Evans, David (World Bank Blogs, 2017)
Technology in education is often seen as a solution. It holds promise, but caution is warranted.Photo: Charlotte Kesl / World Bank There is no denying that governments around the world are expanding investments in education technology, from inputs that students use directly (like Kenya’s project to put tablets in schools) to ...
KerkoCite.ItemAlsoKnownAs: 2339240:LU3TS2MY 2405685:R238S3X3

A Study on the Implementation of the Strengthening Innovation and Practice in Secondary Education Initiative for the preparation of Science, Technology, English and Mathematics (STEM) Teachers in Kenya to integrate Information and Communication Technology (ICT) in Teaching and Learning - Hooker, Mary (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:HGF73GAE 2405685:2RW7F2AH

This BRCK Will Revolutionize Education In Africa - Shapshak, Toby (Forbes, 2015)
In a scene not unlike classrooms around the world, the faces of 40 children glow from the light of their tablets as their teacher leads them through the morning's lesson. Except this happened yesterday inside a converted shipping container in a low-income area of Kenya, in a country where the price [...]
Section: Tech KerkoCite.ItemAlsoKnownAs: 2339240:C43YEZGM 2405685:F48ZHXRT

Assessing the Impact of Early Learning Programs in Africa - Gove, Amber; Brunette, Tracy; Bulat, Jennae; Carrol, Bidemi; Henny, Catherine; Macon, Wykia; Nderu, Evangeline; Sitabkhan, Yasmin (New Directions for Child and Adolescent Development, 2017)
We present results from early learning programs in six African countries: Ethiopia, Kenya, Liberia, Malawi, Tanzania, and Uganda. In partnership with ministries of education, RTI International has worked within government systems to support the design and deployment of locally contextualized materials, training, and assessment tools, with the goal of improving outcomes for early learners in primary schools, and in Kenya and Tanzania preprimary as well. Here we report on the experience and evidence of impact from specific programs in each country, including summary assessment results when available. In several countries with completed impact evaluations, there are significant and important learning gains of between 0.2 and 2.57 SD in effect size; in one case the percentage of students reaching grade‐level reading proficiency increased from 12% to 47%. In the context of increased urgency surrounding what UNESCO has called a “global learning crisis,” these experiences provide useful lessons for policymakers and practitioners alike.
shortDOI: 10/gf86mm KerkoCite.ItemAlsoKnownAs: 10.1002/cad.20224 10/gf86mm 2405685:B4LHC2GD

A Kenyan Cloud School. Massive Open Online & Ongoing Courses for Blended and Lifelong Learning - Jobe, William (Open Praxis, 2013)
This research describes the predicted outcomes of a Kenyan Cloud School (KCS), which is a MOOC that contains all courses taught at the secondary school level in Kenya. This MOOC will consist of online, ongoing subjects in both English and Kiswahili. The KCS subjects offer self-testing and peer assessment to maximize scalability, and digital badges to show progress and completion to recognize and validate non-formal learning. The KCS uses the Moodle LMS with responsive web design to increase ubiquitous access from any device. Access is free and open, and the KCS intends to be a contextualized open educational resource for formal secondary institutions to support blended learning and a free source of non-formal education for lifelong learning. The expected outcomes are that this effort will reduce secondary school dropout rates, improve test scores, become a quality resource for blended learning, as well as validate and recognize lifelong learning in Kenya.
KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.5.4.86 2339240:Q7HX7UH7 2405685:KHRJVC79

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR10.100 2339240:B8RGF7UM 2405685:ZSVGWH7J

Principals' Instructional Leadership Styles and their effect on Tutors on ICT integration in teaching Science - Omwenga, Ezekiel (2016)
The study was carried out to determine the influence of the Principals' leadership style and its effect on the tutors' ICT integration in teaching in Nyanza Region Kenya. One research question and research hypothesis guided the study. The population comprised of 30 Principals and 160 Tutors. A questionnaire and an interview schedule were used to collect data from the Principals and Tutors. Cronbach alpha reliability computation was done to determine the overall reliability of the instrument. Cronbach alpha coefficient of 0.9 and higher was considered reliable. Pearson correlation coefficient, mean and standard deviation were used to analyze data collected and the hypothesis was tested at 0.01 alpha levels. The results from the data analysis indicated there was a direct linear relationship between principal's instructional leadership styles and the teachers' integration of ICT in teaching of science. Based on the findings of the study, it was recommended that the Government of Kenya should develop policies to guide the instructional leaders, KICD, TSC, MOEST and KESI to develop guidelines for Tutors in ICT integration during the teaching of Science.
KerkoCite.ItemAlsoKnownAs: 2339240:EJ4NX3TX 2405685:AJ7SJMEA

Connecting africa using the TV white spaces: from research to real world deployments - Roberts, Sidney; Garnett, Paul; Chandra, Ranveer (The 21st IEEE International Workshop on Local and Metropolitan Area Networks, 2015)
More than 4 billion people are not connected to the Internet. This is either because there is no infrastructure or because Internet access is not affordable. This digital divide is extreme in Africa. At Microsoft, we have been investigating various technologies to bridge this divide. In this paper we describe our research around the TV White Spaces, and how we have leveraged it, and worked with our partners to connect communities in Kenya, Tanzania, Ghana, Botswana, Namibia and South Africa.
KerkoCite.ItemAlsoKnownAs: 10.1109/LANMAN.2015.7114729 2339240:CEDDLEIY 2405685:5QX7YZNE

Learning Equity Requires More than Equality: Learning Goals and Achievement Gaps between the Rich and the Poor in Five Developing Countries - Working Paper 504 - Akmal, Maryam; Pritchett, Lant (RISE Programme Working Paper, 2019)
Achieving some absolute standard of learning for all children is a key element of global equity in education. Using the Annual Status of Education Report (ASER) data from India and Pakistan, and Uwezo data from Kenya, Tanzania, and Uganda that test all children of given ages, whether in school or not, on simple measures of learning in math, reading (local language), and English, we quantify the role of achieving equality between the richest 20% and the poorest 40% in terms of grade attainment and learning achievement toward accomplishing the global equity goal of universal numeracy and literacy for all children.
KerkoCite.ItemAlsoKnownAs: 2339240:HR2A7JWR 2405685:5DCJE3IG

Building Stronger Education Systems: Stories of Change (Global Partnership for Education, 2019)
The Global Partnership for Education (GPE) supports close to 70 developing countries to ensure that every child receives a quality education. The featured stories in this report show the progress that developing country partners are making in getting more children, especially girls, in school and learning. The results are not only evidence of their commitment to improve education, but also of the sustained and targeted support provided by GPE. Feature stories are included from the following countries: (1) Afghanistan; (2) Benin; (3) Burkina Faso; (4) Djibouti; (5) Eritrea; (6) Ethiopia; (7) Guyana; (8) Kenya; (9) Pakistan; (10) Papua New Guinea; and (11) Sudan.
Publication Title: Global Partnership for Education KerkoCite.ItemAlsoKnownAs: 2339240:MHPT5FM3 2405685:8XCGNDGA
Keywords: Access to Education; Barriers; Developing Nations; Disadvantaged; Early Childhood Education; Economic Development; Educational Change; Educational Improvement; Educational Needs; Educational Practices; Educational Quality; Equal Education; Foreign Countries; Reading Instruction; Reading Skills; Refugees; Rural Education; Technology Uses in Education; Womens Education

Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count? - Akyeampong, Kwame; Lussier, Kattie; Pryor, John; Westbrook, Jo (International Journal of Educational Development, 2013)
Teacher education has an important role in ensuring quality of learning especially for the poorest children. The article draws on a study of teacher preparation for the early primary grades in six African countries – Ghana, Kenya, Mali, Senegal, Tanzania and Uganda – in reading and mathematics. Initial teacher education had the strongest impact on newly qualified teachers but also induced misplaced confidence leading to standardised teacher-led approaches that failed to engage learners. Learning to read was divorced from meaning while mathematical activities were not linked to learning concepts. We suggest that teacher education is reconstructed as a study of classroom practice that places children's learning at its centre.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2012.09.006 2339240:TMXTTDED 2405685:CRQY6GMS

Technical and vocational education and training (TVET) for young people in low- and middle-income countries: a systematic review and meta-analysis - Tripney, Janice S; Hombrados, Jorge G (Empirical Research in Vocational Education and Training, 2013)
The world is facing a worsening youth employment crisis. In response, technical and vocational education and training (TVET) is back on the development agenda after years of neglect. This systematic review examined the evidence from studies evaluating the impacts of TVET interventions for young people in low- and middleincome countries (LMICs). The 26 included studies evaluated 20 different interventions, predominantly from Latin America. Meta-analyses of the effectiveness of TVET on five outcome measure categories were conducted. The overall mean effects on overall paid employment, formal employment, and monthly earnings were small, positive, and significant; however, significant heterogeneity was observed. Moderator analysis was performed in an attempt to explain between-study differences in effects. The overall paucity of research in this area, together with specific gaps and methodological limitations, affirm the need for strengthening the evidence base. Implications for policy, practice and research are discussed.
shortDOI: 10/gf62zx KerkoCite.ItemAlsoKnownAs: 10.1186/1877-6345-5-3 10/gf62zx 2317526:ZDA23HGH 2339240:T35VA5TJ 2405685:RC3867EU UA-ef9e8a77-a2ae-48e7-aee2-7ad36c907bed
Keywords: -AB-Review; -AB-Review-SSA; -RQAsummary; -codedOrSummarised; -review; C:Kenya; CLL:en; FF1.1/3; FF2.2; FF2.7.a; interesting; keyReview en; onLongList; retain_obsolete; revofrevSummarisedSeptember2018; summarised

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (Proceedings of the European Conference on e-Government, ECEG, 2012)
Teachers in rural parts of Kenya lack opportunities for professional development (PD). In addition, the teachers have no access to eLearning opportunities like their colleagues in urban parts. Among the factors that do not favor Kenyan rural teachers’ access to PD through eLearning include: lack of access to relevant technologies and lack of electricity. This paper shares research findings on provision of teachers’ PD through a blended learning approach, utilizing appropriate technologies in a rural school in western Kenya. Ten teachers and two Professional Development Teachers (PDTs) participated in this research. In the study, teachers’ needs assessment was done, to inform the instructional design on the topic: How to teach a large class of mixed ability students. The PD was implemented by engaging teachers in a variety of activities including: pairs of teachers collaboratively using a tablet to access self-study content; teachers studying through multimedia content; teachers planning and delivering lessons using activity-based learning and cooperative learning approaches; and PDTs and teachers participating in fortnightly face-to-face meetings. The findings of the study suggest that teaching practices of rural educators can be improved working with local experts to create locally-relevant content for needs-based PD, implemented in a blended learning approach while providing technology stewardship. Teachers accessed and studied through offline content; planned for and implemented cooperative learning and activity-based learning in lessons, using locally available materials; engaged in reflective conversations on successes and challenges; and spontaneously engaged in very lively professional dialogues. While teachers appreciated that it took long to prepare for active learning lessons, it was less strenuous to implement the lessons, because the students took responsibility for their own learning.
KerkoCite.ItemAlsoKnownAs: 2339240:24H28YGJ 2339240:ISIT39J6 2405685:5KI53BLU 2405685:W7KJBF6N 2405685:X3EGT59M 2405685:ZHM4CF5K 2534378:7IHB745E 2534378:SU4VP6FM
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096499; __finaldtb; ⛔ No DOI found

Pathways to Educational Success Among Refugees: Connecting Locally and Globally Situated Resources - Dryden-Peterson, Sarah; Dahya, Negin; Adelman, Elizabeth (American Educational Research Journal, 2017)
This study identifies pathways to educational success among refugees. Data are from an original online survey of Somali diaspora and in-depth qualitative interviews with Somali refugee students educated in the Dadaab refugee camps of Kenya. This research builds on Bronfenbrenner’s ecological model to consider both the locally and globally situated nature of resources across refugees’ ecosystems. Analysis examines the nature and content of student-identified supports and their perceived influence on access to and persistence in school as well as the mediating role of technology. The findings suggest consideration of both locally situated relationships and globally situated relationships as critical educational supports. Implications include leveraging naturally occurring virtual relationships to support educational success of refugees and other young people who are physically isolated from access to needed supports in their local region.
Publisher: American Educational Research Association shortDOI: 10/ggjrsj KerkoCite.ItemAlsoKnownAs: 10.3102/0002831217714321 10/ggjrsj 2339240:8ABCDXEX 2405685:V8STHZKK
Keywords: Google Scholar/ refugee education technology; RER theme_pedagogies and modalities

Studying engagement and performance with learning technology in an African classroom - Mutahi, Juliet; Kinai, Andrew; Bore, Nelson; Diriye, Abdigani; Weldemariam, Komminist (Proceedings of the Seventh International Learning Analytics & Knowledge Conference, 2017)
In this paper, we study the engagement and performance of students in a classroom using a system the Cognitive Learning Companion (CLC). CLC is designed to keep track of the relationship between the student, content interaction and learning progression. It also provides evidence-based engagement-oriented actionable insights to teachers by assessing information from a sensor-rich instrumented learning environment in order to infer a learner's cognitive and affective states. Data captured from the instrumented environment is aggregated and analyzed to create interlinked insights helping teachers identify how students engage with learning content and view their performance records on selected assignments. We conducted a 1 month pilot with 27 learners in a primary school in Nairobi, Kenya during their maths and science instructional periods. We present our primary analysis of content-level interactions and engagement at the individual student and classroom level.
KerkoCite.ItemAlsoKnownAs: 10.1145/3027385.3027395 2339240:WZZYKWZV 2405685:UACDVUZC
Keywords: developing countries; education; engagement; learning analytics; mobile development

Using educational technology to develop early literacy skills in Sub-Saharan Africa - Abrami, Philip C.; Wade, C. Anne; Lysenko, Larysa; Marsh, Jonathon; Gioko, Anthony (Education and Information Technologies, 2016)
The research explores the impact of interactive, multimedia literacy software (ABRA) on the reading skills of early elementary students in Kenya. Twelve grade two English teachers and their students from six schools were randomly divided in half: an experimental group (N = 180) where ABRA was part of their English Language instruction and a control group (N = 174) where regular instruction was used. After the pre-test student data were collected, a three-day initial training and planning session were held for the experimental teachers on how to use ABRA to teach literacy. Every week each experimental class was bussed to a computer lab with full access to ABRA for one 90-min lesson. Teacher support included the alignment of ABRA lesson plans with the Kenyan English Language norms, weekly web conferences with the trainer, as well as technical and pedagogical help from staff at the lab site. After the 13-week intervention, significant and substantial gains in reading comprehension were found for ABRA students as measured by GRADE, a standardized test of literacy. In addition, ABRA students outperformed their peers in control classes on the core end-of-year subject exams including English, Mathematics, Science and Social Studies.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-014-9362-4 2405685:N962IUNP 2486141:YREU5G6T
Keywords: Developing countries; Early literacy; Educational technology; Primary education

Support to children’s education in the urban slums of Nairobi: community and parents’ perceptions with an expanded phase of an education intervention program - Abuya, Benta A.; Wekulo, Patricia; Muhia, Nelson (Qualitative Research in Education, 2018)
The objective of this paper is to examine the perceptions of community elders and parents on their roles regarding support to their children’s education. Data come from the qualitative component of a baseline survey conducted in Korogocho and Viwandani, two urban informal settlements in Nairobi, Kenya. Data were collected in April-May 2016 through in-depth interviews, key informant interviews and focus group discussions. Results demonstrated that community elders internalized their role as the face of government in their respective communities, and enforced the implementation of education policies on behalf of all children. The community leaders also saw as part of their role the need to encourage parents to be active participants in their children’s education. Female parents with boys in the program perceived that parental monitoring and follow-up was important to ensure that their children attended school, and completed work assigned by the teachers, more so in Korogocho. Overall, parents recognized the importance of the role they played in their children’s education. This is a good entry point as parental support will ensure the success and sustainability of the intervention to improve educational outcomes for children, which in turn will help their children navigate the challenging period that adolescence presents.
Number: 2 KerkoCite.ItemAlsoKnownAs: 10.17583/qre.2018.3240 2339240:RWE4QDVW 2405685:UBUMJHXV
Keywords: teachers

Policy interventions for attraction and retention of female teachers in rural secondary schools - Kamere, Isabela M.; Makatiani, M. I.; Nzau, Arthur Kalanza (Msingi Journal, 2019)
The potential role of female teachers in achieving the Education for all (EFA) and the Sustainable Development Goals, specifically on ensuring inclusive and equitable quality education and promoting life-long learning opportunities for all (Goal 4), achieving gender equality and empowering all women and girls(Goal 5 ) is well documented. Available evidence, however, suggests that attraction and retention of female teachers in secondary schools located in rural areas remains a significant and on-going challenge. In response, policy makers in Kenya have recommended three key policy interventions namely decentralization of teacher recruitment, payment of hardship allowance and provision of housing. A literature search reveals a dearth of information on the perspectives of rural educators on the effectiveness of these interventions. The paper presents findings based on one objective of a broader study which was to: Establish the views of female teachers’ and other stakeholders’ regarding the effectiveness of strategies for attraction and retention of female teachers in Makueni County. This study adopted a mixed methods design. The paper presents findings from the qualitative component of the study. Interviews were used to gather data. Based on their interpretations, the authors provide useful insights and offer suggestions on how the implementation of these policies could be improved.
Number: 2 KerkoCite.ItemAlsoKnownAs: 10.33886/mj.v1i2.103 2339240:LPDCWUDG 2405685:RTKRV2ZQ
Keywords: Attraction; female teachers; retention

GraphoGame – a catalyst for multi-level promotion of literacy in diverse contexts - Ojanen, Emma; Ronimus, Miia; Ahonen, Timo; Chansa-Kabali, Tamara; February, Pamela; Jere-Folotiya, Jacqueline; Kauppinen, Karri-Pekka; Ketonen, Ritva; Ngorosho, Damaris; Pitkänen, Mikko; Puhakka, Suzanne; Sampa, Francis; et al. (Frontiers in Psychology, 2015)
GraphoGame (GG) is originally a technology-based intervention method for supporting children with reading difficulties. It is now known that children who face problems in reading acquisition have difficulties in learning to differentiate and manipulate speech sounds and consequently, in connecting these sounds to corresponding letters. GG was developed to provide intensive training in matching speech sounds and larger units of speech to their written counterparts. GG has been shown to benefit children with reading difficulties and the game is now available for all Finnish school children for literacy support. Presently millions of children in Africa fail to learn to read despite years of primary school education. As many African languages have transparent writing systems similar in structure to Finnish, it was hypothesized that GG-based training of letter-sound correspondences could also be effective in supporting children’s learning in African countries. In this article we will describe how GG has been developed from a Finnish dyslexia prevention game to an intervention method that can be used not only to improve children’s reading performance but also to raise teachers’ and parents’ awareness of the development of reading skill and effective reading instruction methods. We will also provide an overview of the GG activities in Zambia, Kenya, Tanzania, and Namibia, and the potential to promote education for all with a combination of scientific research and mobile learning.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2015.00671 2339240:Q4965Q6E 2405685:FW2VAUDE

An Investigation into Implementation of ICT in ECD and Primary Schools, in the Light of Free Laptops at Primary One: a case study of teachers implementing ICT into their teaching practice - Tonui, Betty C.; Kerich, E.; Koross, R.; J, K.; Moi, Too (2018)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley
KerkoCite.ItemAlsoKnownAs: 2339240:CHUK8BFL 2405685:CD7SSBUP

Providing access to education in Sub-Saharan countries through Content-Oriented technology - Kiboro, Angelica; Bailey, Sheena; Nair, Mrinay; Salam, Tomisin; Dwhytie, Alex (2014 IEEE Canada International Humanitarian Technology Conference - (IHTC), 2014)
Access to education has been a growing concern for children in developing economies, namely lack of access to quality customized online content in the classroom and at home; lack of tools that make learning fun and effective in key subject areas; and lack of state resources to meet educational demands. The Rumie Initiative was founded to tackle these concerns. It is a non-profit organization bringing educational content to the world's underprivileged children through low-cost technology. The Rumie Initiative's vision is to redefine the way education is provided, and through this, significantly reduce poverty and drive economic development. The primary advantage of The Rumie Initiative over all other educational technology solutions is that its content is specifically tailored to meet the local educational needs and curriculum standards. Utilizing the vast reserves of free online updated educational content available today; these android driven tablets are an affordable and intuitive way to deliver pre-loaded content without the requirement of internet access. Through mass global volunteerism, The Rumie Initiative collaborates with educators in choosing appropriate educational content and distributes content-loaded tablets through local Non-Governmental Organizations, communities and government entities. The Rumie Initiative has started a program of trials around the world and recently received a positive response at a Computer - Based Math Education Summit in New York hosted by UNICEF from November 21st to 22nd 2013. The initiative was first launched in Haiti on 25th October 2013 and has since, been gaining momentum, currently exploring opportunities in Sub-Saharan countries such as Ghana, Kenya, Uganda, Rwanda, Burundi, South Africa and Nigeria. This paper focuses on The Rumie Initiative's unique business model to reach the masses, emphasizing issues relating to the power of volunteer ism, the forging of strategic development partners, and content-oriented technologies in increasing access to education.
ISSN: null KerkoCite.ItemAlsoKnownAs: 10.1109/ihtc.2014.7147542 10/ggn3tg 2339240:5H77UWY6 2405685:XF5UPDR7
Keywords: Blogs; Communities; Education; Internet; Internet access; Monitoring; Organizations; Rumie initiative; Servers; Terminology; authorisation; computer aided instruction; content management; content-oriented technology; curriculum standards; economics; economies; educational content; educational demands; government entities; non-governmental organizations; online content; standards; sub-Saharan countries

Technology for Inclusive Education (TFIE) Pilot Report - Digital Literacy Trust (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:SH5FCHUZ

Gender responsive pedagogy: A toolkit for teachers and schools. 2nd ed. - FAWE (Forum for African Women Educationalists (FAWE)., 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:H5QIUE3J 2405685:WMBZ8VMB

Accelerated Education Programme Youth Education Programme: NRC Education Scale-up and Quality Fund, EdTech for Rapid Response in Acute Emergencies Project - Kipruto, Amos; Denny, Kathleen (Norwegian Refugee Council, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:3FEKJXY2 4042040:B3V7LHH4

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2013)
It is widely recognised that the foreign aid system - which today involves every country in the world - is in need of drastic change. But there are conflicting opinions as to what is needed. Some call for dramatic increases in resources, to meet long-overdue commitments, and to scale up what is already being done around the world. Others point to the flaws in aid, and bang the drum for cutting it altogether - and argue that the fate of poor and vulnerable people be best placed in the hands of markets and the private sector. Meanwhile, growing numbers are suggesting that what is most needed is the creative, innovative transformation of how aid works. Aid on the Edge of Chaos is firmly in the third of these camps. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions on which foreign aid is built would be more at home in early twentieth century factory floors than in the dynamic, complex world we face today. All around us, we can see the costs and limitations of dealing economies and societies as if they are analogous to machines. The reality is that such social systems have far more in common with ecosystems: they are complex, dynamic, diverse and unpredictable. Many thinkers and practitioners in science, economics, business, and public policy have started to embrace more 'ecologically literate' approaches to guide both thinking and action, informed by ideas from the 'new science' of complex adaptive systems. Inspired by these efforts, there is an emerging network of aid practitioners, researchers, and policy makers who are experimenting with complexity-informed responses to development and humanitarian challenges. This book showcases the insights, experiences, and often remarkable results from these efforts. From transforming approaches to child malnutrition, to rethinking processes of economic growth, from building peace to combating desertification, from rural Vietnam to urban Kenya, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. Ramalingam argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.
KerkoCite.ItemAlsoKnownAs: 2405685:JI2589JZ

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:CNU2GKRL 2339240:KPPU5Z99 2339240:RNRNDVLK 2339240:S2XT5FSG 2339240:UYNN98AQ 2339240:Z8QK9TIS 2405685:4JNZ9RRF 2405685:58SRHUVT 2405685:CF2KPK7I 2405685:DJG72BUZ 2405685:FXXS4882 2405685:LW3BSKJ4 2405685:ZEBNC5TV 2534378:6GQU9R37 2534378:ARJJXBIL 2534378:TQ4YR37L 2534378:WSS9V2GJ 2534378:XIMVL4RJ
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC; Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Approved Basic Education Statistical Booklet 2019 - Ministry of Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:JFBPSH7S 2405685:GBA7WEDP

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Are Our Children Learning? - Uwezo (Twaweza East Africa, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:8P9EDHXN 2405685:N3RG9SY9

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets